Water dispersion of vinylidene chloride copolymer, film, and paper laminate

The aqueous dispersion of vinylidene chloride copolymer with integrated ultraviolet absorption addresses the challenge of combining gas barrier and ultraviolet protection in films, offering efficient and cost-effective protection for packaged contents.

JP2025012584APending Publication Date: 2025-01-24ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023115512
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing films with gas barrier properties do not effectively combine ultraviolet absorption, and methods to integrate ultraviolet absorbers often increase production costs, reduce adhesion strength, and are not environmentally friendly, particularly when using organic solvents.

Method used

Aqueous dispersion of vinylidene chloride copolymer with a polymerization layer that includes structural units derived from ultraviolet absorbing monomers, ensuring uniform distribution and absorption of ultraviolet rays without the need for separate layers or organic solvents, maintaining gas barrier properties.

Benefits of technology

The solution provides a film with both gas barrier and ultraviolet absorption capabilities, ensuring effective protection of contents from ultraviolet light while being environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012584000001
    Figure 2025012584000001
  • Figure 2025012584000002
    Figure 2025012584000002
  • Figure 2025012584000003
    Figure 2025012584000003
Patent Text Reader

Abstract

To provide a water dispersion of a vinylidene chloride copolymer having both of gas barrier property and ultraviolet absorption property, and a film and a paper laminate having a layer constituted by coating with the water dispersion.SOLUTION: A water dispersion of a vinylidene chloride copolymer having an absorption coefficient at a wave length of 360 nm of 0.01 L / (g cm) or higher includes: 100 pts.mass of a vinylidene chloride copolymer; 0 pts.mass or more and 20 pts.mass or less of a macromolecular compound other than the vinylidene chloride copolymer, where the content of a structural unit derived from vinylidene chloride in the vinylidene chloride copolymer is 80 mass% or more. A film or a paper laminate has a vinylidene chloride copolymer layer constituted by coating with a water dispersion of a vinylidene chloride copolymer having an absorption coefficient at a wave length of 360 nm of 0.01 L / (g cm) or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion of a vinylidene chloride copolymer, a film, and a paper laminate. More specifically, the present invention relates to an aqueous dispersion of a vinylidene chloride copolymer having ultraviolet absorbing properties, and a film and a paper laminate having a layer formed by applying the aqueous dispersion. [Background technology]

[0002] In order to maintain the quality of food and medicine, the film used to package them must adequately block and seal gases in the atmosphere, such as oxygen, nitrogen, carbon dioxide, and water vapor. In this regard, among various resins, a film having a layer formed from an aqueous dispersion of a vinyl halide copolymer, particularly an aqueous dispersion of a vinylidene chloride copolymer, has excellent barrier properties against water vapor and oxygen, and is therefore very suitable for food and medicine packaging applications. Besides gas, ultraviolet light is also a factor that accelerates the deterioration of food and medicines. To protect the contents from ultraviolet light, films with ultraviolet absorbing properties are widely used.

[0003] In recent years, packaging films are required to have both gas barrier properties and UV absorption properties in order to maintain the quality and efficacy of pharmaceuticals and food ingredients for a longer period of time. In addition, there is a strong global demand to reduce the use of petroleum, a finite resource, and the more excellent functionality can be imparted with a smaller amount of carbon, the higher the value of the material. From the perspective of reducing petroleum use, it is also useful to reduce the energy required for film production. Naturally, these films are also required to be commercially produced at low cost.

[0004] Vinylidene chloride copolymers are known to have high gas barrier properties, and aqueous dispersions of these copolymers are widely used as gas barrier coating agents. Compared to solvent-based coating agents, they do not require organic solvents because they use water as a solvent, and therefore have various advantages in terms of cost, working environment, and environmental impact. Known vinylidene chloride copolymer aqueous dispersions constituting a film having gas barrier properties are described in Patent Documents 1 to 7. Known films having both gas barrier properties and ultraviolet absorbing properties are described in Patent Documents 8 to 11.

[0005] In addition, in recent years, the importance of recycling plastics has been increasing. As described in Patent Documents 1 to 7, in the case of a multilayer film in which an aqueous dispersion that imparts gas barrier properties is applied to a substrate, each layer is peeled off and separated by resin type for recycling. In the case of a multilayer film, the recyclability of the substrate, which accounts for the majority of the weight, is most important. Since a substrate that does not contain additives such as ultraviolet absorbers has a higher value as a recycled raw material, there is a need to avoid adding ultraviolet absorbers to the substrate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2013 / 125699 [Patent Document 2] Special Publication No. 2001-526315 [Patent Document 3] Japanese Patent Application Publication No. 05-202107 [Patent Document 4] JP 2018-127523 A [Patent Document 5] Japanese Patent Application Laid-Open No. 60-192768 [Patent Document 6] French Patent No. 1466220 [Patent Document 7] Special Publication No. 2009-541565 [Patent Document 8] JP 2004-51174 A [Patent Document 9] Japanese Patent Application Laid-Open No. 63-128033 [Patent Document 10] : Japanese Patent Application Publication No. 62-263045 [Patent Document 11] : JP 2013-151598 A Summary of the Invention [Problem to be solved by the invention]

[0007] The vinylidene chloride copolymers described in Patent Documents 1 to 7 have excellent gas barrier properties after coating, but do not have ultraviolet ray absorbing ability. Patent Document 8 describes a method of laminating an ultraviolet absorbing layer separately from a gas barrier layer. Although this method achieves the objective of providing both gas barrier properties and ultraviolet absorbing properties, it is undesirable from the viewpoints of energy efficiency and cost because it requires the use of a binder resin to provide the ultraviolet absorbing layer and the steps of producing the gas barrier layer and the ultraviolet absorbing layer separately. Patent Document 9 describes a method of dissolving an ultraviolet absorber in the undercoat layer, but this method has the problems that it requires a step of dissolving the ultraviolet absorber before use, which is costly, and that the thickness of the undercoat layer is small, so sufficient ultraviolet absorption cannot be obtained unless a large amount of ultraviolet absorber is dissolved. Addition of an excessive amount of ultraviolet absorber leads to a decrease in adhesion strength and an increase in dissolution time. In addition, it has the disadvantage that it is limited to an organic solvent-based undercoat layer and cannot be applied to water-based undercoats that are less harmful to the environment and workers. Patent Document 10 describes a method for preparing a vinylidene chloride copolymer layer having both ultraviolet absorbing ability and gas barrier ability by dissolving a vinylidene chloride copolymer in an organic solvent and simultaneously dissolving an ultraviolet absorber. This method is not preferable because it requires a step of dissolving the ultraviolet absorber uniformly in the solvent and uses an organic solvent that is expensive and has a high environmental impact compared to water. In addition, unlike the aqueous dispersion coats described in Patent Documents 1 to 7, it cannot be coated over, and there is also a problem that the gas barrier property is limited. Patent Document 11 describes a mixture of an aqueous dispersion of a vinylidene chloride copolymer and an acrylic copolymer, and suggests that the aqueous dispersion of the acrylic copolymer can be given ultraviolet light absorption ability, but a large amount of the acrylic copolymer is used, and the resulting film exhibits only low gas barrier properties. In addition, the use of a large amount of the acrylic copolymer impairs the transparency of the film, causing problems with visibility of the contents when used as a packaging material. Patent documents 1 to 7 and 10 suggest adding an ultraviolet absorber to an aqueous dispersion of vinylidene chloride copolymer, but Patent document 10 also describes that there is a problem with uniform dispersion. The ultraviolet absorber described in Patent document 10 does not exhibit water dispersibility, so even if it is added, it will simply precipitate and it is not possible to impart ultraviolet absorbing ability to the aqueous dispersion. Furthermore, Patent documents 1 to 7 do not describe a specific method for adding the ultraviolet absorber. As described above, these documents do not suggest any examples of uniformly dispersing an ultraviolet absorber in an aqueous dispersion while maintaining gas barrier properties.

[0008] Therefore, an object of the present invention is to provide an aqueous dispersion of a vinylidene chloride copolymer that combines gas barrier properties and ultraviolet absorbing properties, and a film and a paper laminate having a layer formed by applying the aqueous dispersion. [Means for solving the problem]

[0009] That is, the present invention is as follows. [1] An aqueous dispersion of vinylidene chloride copolymer with an absorption coefficient of 0.01 L / (g cm) or more at a wavelength of 360 nm. The composition contains 0 parts by mass or more and less than 20 parts by mass of a polymer compound other than the vinylidene chloride copolymer, based on 100 parts by mass of the vinylidene chloride copolymer; The content of structural units derived from vinylidene chloride in the vinylidene chloride copolymer is 80% by mass or more. 1. An aqueous dispersion comprising: [2] The aqueous dispersion according to [1], wherein the aqueous solution obtained by extracting the water-soluble component with water has an absorbance at a wavelength of 360 nm of less than 0.4. [3] The aqueous dispersion according to [1] or [2], containing a polymeric ultraviolet absorber. [4] The aqueous dispersion according to [3], wherein the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer and a structural unit derived from vinylidene chloride. [5] A film or paper laminate comprising a vinylidene chloride copolymer layer coated with the aqueous dispersion according to any one of [1] to [4]. [6] 1. A film or paper laminate comprising a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of a vinylidene chloride copolymer, the vinylidene chloride copolymer layer having an absorption coefficient of 0.01 L / (g cm) or more at a wavelength of 360 nm. [7] The film or paper laminate according to [5] or [6], wherein the layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorber. [8] The film or paper laminate according to any one of [5] to [7], wherein an aqueous solution obtained by extracting the water-soluble components with water has an absorbance at a wavelength of 360 nm of less than 0.4. [9] The film or paper laminate according to any one of [5] to [8], wherein the vinylidene chloride copolymer layer contains a polymeric ultraviolet absorber.

[10] The film or paper laminate according to [9], wherein the vinylidene chloride copolymer contains structural units derived from an ultraviolet absorbing monomer and structural units derived from vinylidene chloride. Effect of the Invention

[0010] According to the present invention, it is possible to provide an aqueous dispersion of a vinylidene chloride copolymer that combines gas barrier properties and ultraviolet absorbing properties, as well as a film and a paper laminate having a layer formed by applying the aqueous dispersion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its gist.

[0012] [Water dispersion of vinylidene chloride copolymer] The aqueous dispersion of vinylidene chloride copolymer (hereinafter, simply referred to as "aqueous dispersion"), which is a first aspect of this embodiment, is in the form of particles of vinylidene chloride copolymer dispersed in an aqueous solvent. The content of the organic solvent contained in the aqueous solvent is preferably 5 parts by mass or less, more preferably less than 1 part by mass, and particularly preferably 0 part by mass, when the mass of water is 100 parts by mass. The inclusion of an organic solvent is undesirable from the viewpoints of the working environment, environmental load, equipment deterioration, and flammability of the solvent. The aqueous dispersion of vinylidene chloride copolymer of this embodiment has an absorption coefficient ε1 of 0.01 L / (g·cm) or more at a wavelength of 360 nm, which is generally referred to as ultraviolet light. The absorption coefficient ε1 is preferably 0.03 L / (g·cm) or more, more preferably 0.08 L / (g·cm) or more, even more preferably 0.14 L / (g·cm) or more, and even more preferably 0.29 L / (g·cm) or more. The greater the absorption coefficient ε1 of the aqueous dispersion, the more the deterioration of the contents, the substrate, and the vinylidene chloride copolymer itself due to ultraviolet light can be suppressed when a film coated with the aqueous dispersion is used as a packaging material. The absorption coefficient ε1 of the aqueous dispersion is preferably 1.00 L / (g·cm) or less, more preferably 0.76 L / (g·cm) or less, and even more preferably 0.61 L / (g·cm) or less. Examples of methods for controlling the extinction coefficient ε1 include methods for increasing the absorbance at a wavelength of 360 nm by adding an ultraviolet absorber to the aqueous dispersion or synthesizing vinylidene chloride copolymer using an ultraviolet absorbing monomer, as described below.

[0013] The absorbance at a wavelength of 360 nm can be measured using UV-Vis spectroscopy. In this specification, measurement using ultraviolet-visible spectroscopy means measurement under the following conditions. <If the sample is a film> The absorbance of the film is measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc. The measurement conditions are as follows. Field of view: 10° Main light source: D65 Secondary light source: None <If the sample is liquid> The absorbance is measured using a UV-Visible spectrophotometer UV1280 manufactured by Shimadzu Corporation. Reference: Sample solvent (THF if the sample was dissolved in THF) Cell: Quartz cell (optical path length 1 cm)

[0014] The method for calculating the absorption coefficient ε1 at a wavelength of 360 nm will be described. A water dispersion of vinylidene chloride copolymer was applied to aluminum foil at a coating weight of 10 g / m2 after drying. 2 The solution is applied so that the concentration becomes 0.2% by mass, and then dried in a hot air dryer at 100°C for 1 minute to obtain a dried product. If the solution is liquid or there is still moisture remaining, dry it in an oven for a few more minutes until it is no longer liquid. The dried product is added to tetrahydrofuran so that the concentration becomes 0.2% by mass, and dissolved by stirring at room temperature. If any residue remains, heat and stir the solution to the extent that the tetrahydrofuran does not boil, and if it still does not dissolve, filter the liquid to remove the insoluble matter. The longer the heating time, the more likely the vinylidene chloride copolymer is to discolor due to heat, so the shorter the heating time and the lower the temperature, the better. The solution obtained is measured using the above-mentioned ultraviolet-visible spectroscopy <when ​​the sample is liquid> to obtain the absorbance A1 at a wavelength of 360 nm. If the concentration of the dry matter dissolved in tetrahydrofuran is x [g / L], the extinction coefficient ε1 [L / (g cm)] can be calculated using the Beer-Lambert equation below. Beer-Lambert equation: A1=ε1×x×l (l: optical path length [cm]) Normally, the absorbance at a wavelength of 360 nm is governed by the content of the ultraviolet absorber, so even if a vinylidene chloride copolymer coating film is coated and dried under conditions different from the measurement method described above, the absorbance remains almost unchanged. Furthermore, when the absorbance A1 exceeds 0.8, the extinction coefficient ε1 cannot be accurately determined, so the concentration of the dried material to be dissolved is appropriately adjusted so that the absorbance falls within the range of 0.1 to 0.8, and then the extinction coefficient is determined.

[0015] (Vinylidene chloride copolymer) The vinylidene chloride copolymer of the present embodiment contains structural units derived from vinylidene chloride (VDC) and structural units derived from a monomer copolymerizable with vinylidene chloride (hereinafter also simply referred to as a "comonomer"). In this specification, the term "vinylidene chloride copolymer" refers to a polymer compound in which the proportion of structural units derived from vinylidene chloride is 50% by mass or more when the total amount of the vinylidene chloride copolymer is taken as 100% by mass.

[0016] Examples of monomers copolymerizable with vinylidene chloride include maleic anhydride; itaconic acid; methyl acrylate (MA), methyl methacrylate (MMA), ethyl acrylate (EA), butyl acrylate (BA), ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, glycidyl acrylate, acrylonitrile (AN), methacrylonitrile (MAN), and the like. (Meth)acrylic monomers such as acrylic acid (AA), methacrylic acid (MAA), acrylamide, N-methylolacrylamide, etc.; 2-acrylamido-2-methylpropanesulfonic acid (AMPS) or a salt thereof (such as the sodium salt); styrene, 2-sulfoethylmethacrylic acid (2-SEM) or a salt thereof (such as the sodium salt); phosphate ester of methacrylate-terminated polypropylene glycol or a salt thereof (such as the sodium salt), vinyl chloride, etc., but are not limited to these, and may be any monomer copolymerizable with vinylidene chloride. The monomers copolymerizable with vinylidene chloride may be used alone or in combination of two or more kinds.

[0017] The vinylidene chloride copolymer of the present embodiment contains 80% by mass or more of structural units derived from vinylidene chloride when the total mass of the vinylidene chloride copolymer is 100% by mass. The content of structural units derived from vinylidene chloride is preferably 85% by mass or more, more preferably 88% by mass or more, even more preferably 89% by mass or more, and even more preferably 90% by mass or more. The more structural units derived from vinylidene chloride there are, the more the resulting coating film tends to have excellent gas barrier properties. By designing the lower limit of the content to be within this range, the coating film of the aqueous dispersion of the vinylidene chloride copolymer will have high gas barrier properties. The content of the structural unit derived from vinylidene chloride is preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less, and even more preferably 93% by mass or less. When the upper limit of the content is designed to be within this range, the coating film of the aqueous dispersion tends to have high flexibility. When the content of the structural unit derived from vinylidene chloride is excessive, the crystallization rate increases significantly, and the elasticity of the vinylidene chloride copolymer particles increases, causing the film-forming property of the aqueous dispersion to decrease over time. Therefore, when the upper limit of the content is designed to be within the above range, an aqueous dispersion of vinylidene chloride copolymer that can maintain good film-forming property for a long period of time tends to be obtained. In addition, in a film coated with an aqueous dispersion of a vinylidene chloride copolymer in which the lower limit of the content of structural units derived from vinylidene chloride is designed to be within the above range, double bonds are generated by dehydrohalogenation reaction of the vinylidene chloride copolymer under ultraviolet light. A polyene structure in which double bonds are linked has the characteristic of absorbing ultraviolet light. In other words, when the film and the contents packaged by the film are exposed to excessive ultraviolet light, the vinylidene chloride copolymer itself changes to a structure that absorbs ultraviolet light. As a result, the film coated with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment can protect the contents from ultraviolet light more reliably than conventional ultraviolet absorbing films. On the other hand, as the proportion of structural units derived from vinylidene chloride increases, the dehydrochlorination reaction is promoted, and there is a tendency for not only ultraviolet light but also visible light to be absorbed. If the upper limit of the content of structural units derived from vinylidene chloride is designed to be within the above range, there is a tendency for excessive discoloration of the film and reduced visibility of the contents to be prevented.

[0018] The content of structural units derived from copolymerization monomers is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 12% by mass or less, still more preferably 11% by mass or less, and particularly preferably 10% by mass or less, based on 100% by mass of the total mass of the vinylidene chloride copolymer. The content of structural units derived from copolymerization monomers is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and still more preferably 7% by mass or more, based on 100% by mass of the total mass of the vinylidene chloride copolymer.

[0019] The content of the structural unit derived from the ultraviolet absorbing copolymerization monomer (ultraviolet absorbing monomer) described later may be appropriately adjusted so that the absorption coefficient ε1 at a wavelength of 360 nm is 0.01 [L / (g·cm)] or more, but is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on 100% by mass of the total mass of the vinylidene chloride copolymer. The content of the structural unit derived from the ultraviolet absorbing monomer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, based on 100% by mass of the total mass of the vinylidene chloride copolymer. When the upper limit of the content of the structural unit derived from the ultraviolet absorbing monomer is within the above range, the risk of the highly hydrophobic ultraviolet absorber precipitating after polymerization and contaminating the polymerization machine tends to decrease, and the coating film after coating tends to exhibit high water vapor barrier properties. Furthermore, the amount of very expensive ultraviolet absorbing monomer used tends to be reduced, making it possible to design products at a realistic cost. In addition, when the lower limit of the content of the structural unit derived from the ultraviolet absorbing monomer is within the above range, the coating film after coating can exhibit sufficient ultraviolet absorbing properties, and when a film coated with the aqueous dispersion is used as a packaging material, the contents tend to be sufficiently protected from ultraviolet rays. In addition, discoloration of the vinylidene chloride copolymer itself due to ultraviolet rays tends to be less likely to occur.

[0020] The monomer composition of the vinylidene chloride copolymer can be evaluated by dissolving a sample obtained by the following method 1) or 2) in tetrahydrofuran-d8 and performing NMR measurement.

[0021] 1) When a water dispersion of vinylidene chloride copolymer is available, a sample for NMR measurement is obtained by the following method. Freeze-dry 10 mL of the aqueous dispersion of vinylidene chloride copolymer, and collect 0.5 g of the freeze-dried product. Completely dissolve the collected freeze-dried product in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or higher. If the freeze-dried product is difficult to dissolve in tetrahydrofuran, it may be heated and stirred within a range where the tetrahydrofuran does not boil. Drop 40 mL of acetone into the obtained solution, and filter the resulting precipitate. Collect the insoluble matter remaining after filtration to use as the measurement sample.

[0022] 2) When an aqueous dispersion of vinylidene chloride copolymer is not available and only a film having a vinylidene chloride copolymer layer coated with the aqueous dispersion is available, a sample for NMR measurement is obtained by the following method. Separate the vinylidene chloride copolymer (layer) from the film having the vinylidene chloride copolymer layer, collect 0.5 g, and completely dissolve it in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or more. If it does not dissolve at room temperature, heat it to 60°C or less to completely dissolve it. Drop 40 mL of acetone into the solution, and filter the resulting precipitate. Collect the insoluble matter remaining after filtration to use as the measurement sample.

[0023] The NMR measurement conditions were as follows. Equipment: JEOL RESONANCE ECS400 (1H), Bruker Biospin Avance600 (13C) Observed nuclei: 1H (399.78MHz), 13C (150.91MHz) Pulse program: Single pulse (1H), zgig30 (13C) Accumulation count: 256 times (1H), 10,000 times (13C) Lock solvent: THF-d8 Chemical shift reference: THF (1H: 180 ppm, 13C: 67.38 ppm) Using the obtained NMR spectrum, the monomers are assigned, and the composition of the vinylidene chloride copolymer is identified by integrating the peaks.

[0024] As an example, for a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate and acrylic acid, 13 In the C-NMR spectrum, the content of structural units derived from vinylidene chloride is determined by integrating from 80 to 90 ppm, the content of structural units derived from methacrylonitrile is determined by integrating from 110 to 130 ppm, the content of structural units derived from methyl methacrylate is determined by integrating from 170 to 180 ppm, and the content of structural units derived from acrylic acid is determined by integrating from 180 to 200 ppm, and the composition ratio of each monomer in the total is calculated.

[0025] In calculating the above composition ratio, the peak of the COOCH3 group (a in the formula below) is integrated to determine the amount of methyl methacrylate. Methyl acrylate is another monomer that also has a COOCH3 group and is often copolymerized with vinylidene chloride. To distinguish between the two, 1 In the H-NMR spectrum, it is judged by the presence or absence of a peak of a methyl group (b in the formula below) bonded to the carbon of the main chain to which the COOCH3 group is bonded. This methyl group is not split because the carbon of the main chain to which it is bonded is not bonded to hydrogen, and the peak position is about 2 ppm. If a monomer having a methyl group other than methyl methacrylate, such as methacrylonitrile, is included, it can be judged by the number of methyl group peaks around 2 ppm. [ka]

[0026] Similarly, acrylonitrile and methacrylonitrile can be distinguished by the presence or absence of a peak for a methyl group (b in the above formula).

[0027] If necessary, the insoluble matter is subjected to additional measurements such as two-dimensional NMR measurement and infrared spectroscopy to identify the monomers. In addition, a copolymer with a known composition may be polymerized and measured in the same manner to compare the results.

[0028] (UV absorber) The wavelength of 360 nm is generally known as the ultraviolet region, and the addition of an ultraviolet absorber is effective in increasing the absorbance at this wavelength. On the other hand, the addition of an excessive ultraviolet absorber impairs the mechanical properties, transparency, and gas barrier properties, and is also undesirable from the viewpoint of cost. Conventionally, it has been difficult to compound an ultraviolet absorbent with an aqueous dispersion of a vinylidene chloride copolymer, because the aqueous dispersion is a heterogeneous substance in which a hydrophobic polymer is dispersed in water, and most ultraviolet absorbents are hydrophobic, so even if they are added, they cannot be dispersed in water and will precipitate. Therefore, it is preferable that the aqueous dispersion of this embodiment contains one or more of a hydrophilic UV absorber, contains emulsified and dispersed hydrophobic UV absorber particles, and at least a portion of the vinylidene chloride copolymer is a vinylidene chloride copolymer having UV-absorbing properties (i.e., the vinylidene chloride copolymer has structural units derived from UV-absorbing monomers), thereby increasing the absorbance at a wavelength of 360 nm and controlling the extinction coefficient ε1 at a wavelength of 360 nm to 0.01 L / (g cm) or more.

[0029] UV absorbents are roughly divided into two types: hydrophilic UV absorbents and hydrophobic UV absorbents. The hydrophobic ultraviolet absorbents can be further classified into polymerizable ultraviolet absorbents having radical polymerizability and non-polymerizable ultraviolet absorbents having no radical polymerizability. Hydrophilic UV absorbers dissolve in water. In food packaging and pharmaceutical packaging applications, water-soluble additives have the risk of migrating into the contents, and are restricted by national laws. On the other hand, they have the advantage of being easily dispersible in aqueous dispersions, and can be used in applications where migration into the contents is not important.

[0030] When the aqueous dispersion contains a hydrophilic ultraviolet absorber, the content of the hydrophilic ultraviolet absorber may be appropriately adjusted so that the absorption coefficient ε1 of the aqueous dispersion at a wavelength of 360 nm is 0.01 [L / (g cm)] or more, but is preferably 5.0 parts by mass or less, more preferably 2.0 parts by mass or less, and even more preferably 0.9 parts by mass or less, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in terms of dry mass. The content of the hydrophilic ultraviolet absorber is preferably 0.1 parts by mass or more, and more preferably 0.5 parts by mass or more, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in terms of dry mass.

[0031] The presence or absence of a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the dried aqueous dispersion of vinylidene chloride copolymer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water dropwise to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the dropwise addition. Since vinylidene chloride copolymer is hydrophobic, it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component.

[0032] When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the water dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when a film coated with the water dispersion is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.

[0033] Hydrophobic UV absorbers are preferable because they have low solubility in water and therefore have a low risk of migrating into the contents when a film coated with the aqueous dispersion is used as a packaging material. On the other hand, they have a problem in that they have low affinity with water, which is the medium of the aqueous dispersion, and therefore require ingenuity for dispersion. Methods for dispersing a hydrophobic ultraviolet absorber in an aqueous dispersion include a method of adding the absorber after emulsification and a method of introducing the absorber into polymer particles constituting an aqueous dispersion of a vinylidene chloride copolymer.

[0034] The emulsification can be carried out by emulsifying the ultraviolet absorber with water and an emulsifier. The average particle size of the obtained emulsion is preferably 200 nm or less, more preferably 100 nm or less. When an aqueous dispersion of a vinylidene chloride copolymer containing an ultraviolet absorber designed to have an average particle size within this range is added, the resulting coating film tends to have excellent transparency. This is because if the particle size of the ultraviolet absorber is large, the ultraviolet absorber will scatter light. The method for preparing an ultraviolet absorber emulsion having a small average particle size is not particularly limited, and any known method can be used. Examples include a method of carrying out emulsion polymerization using a polymerizable ultraviolet absorber, and a method of carrying out emulsion polymerization using a non-polymerizable ultraviolet absorber dissolved in a monomer. In the method of heating a non-polymerizable ultraviolet absorber, water, and an emulsifier, and emulsifying by applying high-speed shear, it is usually difficult to obtain an emulsion with a fine particle size. In addition, the emulsifier suitable for the method of emulsifying by shear is usually not the same as the emulsifier suitable for emulsion polymerization, and it is necessary to use an emulsifier different from the emulsifier used during polymerization of vinylidene chloride copolymer, which is a manufacturing disadvantage in terms of raw material management and cost.

[0035] When the aqueous dispersion contains a non-polymerizable ultraviolet absorber, the content of the non-polymerizable ultraviolet absorber may be appropriately adjusted so that the absorption coefficient ε1 of the aqueous dispersion at a wavelength of 360 nm is 0.01 [L / (g·cm)] or more, but is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably 1 part by mass or less, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in dry mass. The content of the non-polymerizable ultraviolet absorber is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in dry mass.

[0036] The hydrophobic ultraviolet absorber is preferably a polymerizable ultraviolet absorber. The polymerizable ultraviolet absorber becomes a high molecular weight polymer ultraviolet absorber by polymerization. This is preferable because it reduces the risk of migration not only to water but also to organic solvents. In addition, by incorporating the ultraviolet absorber into the polymer main chain, phase separation due to differences in polarity is unlikely to occur, and it is also excellent in terms of transparency and mechanical properties. The polymerizable ultraviolet absorber may be used as a monomer in the polymerization of the vinylidene chloride copolymer of this embodiment. In this case, the vinylidene chloride copolymer contains a structural unit derived from the polymerizable ultraviolet absorber (ultraviolet absorbing monomer) and a structural unit derived from vinylidene chloride, and the vinylidene chloride copolymer of this embodiment itself can be said to be a polymeric ultraviolet absorber. In addition to the polymerization of the vinylidene chloride copolymer, for example, it may be used in the polymerization of the seed latex described later, or in the polymerization of the polymeric ultraviolet absorber emulsion added after polymerization. Since an increase in the amount of ultraviolet absorber added tends to impair gas barrier properties, it is preferable to use it in the polymerization of the seed latex or the polymerization of the vinylidene chloride copolymer. The amount of seed latex used relative to the vinylidene chloride copolymer is usually as small as about 5 parts by mass at most when the total mass of the vinylidene chloride copolymer is 100 parts by mass, so in order to add an effective amount of ultraviolet absorber, a large amount of polymerizable ultraviolet absorber, usually 10 to 30% by mass of the total mass of the seed latex, needs to be polymerized in the polymerization of the seed latex. For example, when the total mass of the vinylidene chloride copolymer is 100 parts by mass, it is desired to introduce 1 part by mass of polymerizable ultraviolet absorber. In that case, when the amount of seed latex used is 3 parts by mass, 33% by mass of polymerizable ultraviolet absorber in the seed latex is required. The use of a large amount of polymerizable ultraviolet absorber exceeding 10% by mass leads to an increase in the residue after polymerization and an increase in the particle size of the seed latex. Therefore, the polymerizable ultraviolet absorber is particularly preferably used for polymerization of the vinylidene chloride copolymer of the present embodiment. Also, the vinylidene chloride copolymer has high chemical resistance, and by copolymerizing the polymerizable ultraviolet absorber (ultraviolet absorbing monomer), the risk of elution of the ultraviolet absorber can be further reduced compared to normal polymeric ultraviolet absorbers, which is preferable.

[0037] By utilizing a solvent gradient chromatography method using a UV detector, the ultraviolet absorber contained in the aqueous dispersion of the vinylidene chloride copolymer of this embodiment can be analyzed. The peak derived from the compound containing the ultraviolet absorber is observed as a large peak. When the peak of the observed vinylidene chloride copolymer is significantly larger than the peak of a standard sample of the vinylidene chloride copolymer in which the ultraviolet absorber is not copolymerized, it can be considered that the ultraviolet absorber (ultraviolet absorbing monomer) is copolymerized in the vinylidene chloride copolymer. Similarly, whether or not an ultraviolet absorbent is copolymerized in the seed latex can be judged by comparing with a standard seed latex sample that does not contain an ultraviolet absorbent. In addition to the above analysis, it is more effective to purify the measurement target by acetone precipitation or methanol precipitation, and if the peak disappears, it is determined that the UV absorber is not copolymerized. If the peak components can be separated, they can be subjected to NMR or other analysis for more detailed analysis.

[0038] Examples of ultraviolet absorbents include benzophenone-based, benzotriazole-based, and triazine-based ultraviolet absorbents.

[0039] Specific examples of the benzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4,4'dimethoxybenzophenone, 2,2',4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, and 2-hydroxy-4-stearyloxybenzophenone. Specific examples of the polymerizable benzophenone-based ultraviolet absorber include 2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, and 2-hydroxy-4-(acryloxy-triethoxy)benzophenone.

[0040] Specific examples of the benzotriazole-based ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3,5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-(2'-hydroxy-3,5'-di-tert-octylphenyl)benzotriazole. , 2-[2'-hydroxy-3,5'-bis(α,α'-dimethylbenzyl)phenyl]benzotriazole, condensation product of methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) ("TINUVIN1130" manufactured by BASF Japan Ltd.), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate nate ("TINUVIN 384" manufactured by BASF Japan Ltd.), 2-(3-dodecyl-5-methyl-2-hydrophenyl)benzotriazole ("TINUVIN 571" manufactured by BASF Japan Ltd.), 2-(2'-hydroxy-3'-tert-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazo 2-[2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2-methylenediphenylbis[4-(1,1,3,3-tetramethylbutyl-6-(2H-benzotriazol-2-yl)phenol], and 2,2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenolethyl)phenol ("TINUVIN900" manufactured by BASF Japan Ltd.). Specific examples of the polymerizable benzotriazole-based ultraviolet absorber include 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole ("RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2"-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate ("CGL-104" manufactured by BASF Japan Ltd.).

[0041] Specific examples of triazine-based ultraviolet absorbers include 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-(2,4-dihydroxyphenyl)-4,6-diphenyl-1,3,5-triazine, and Ethylhexyl Triazone, 2-(2-Hydroxy-4-methoxyphenyl)-4,6-diphenyl-1,3,5-triazine, N,N',N''-Tri(m-tolyl)-1,3,5-triazine-2,4,6-triamine, 2,4,6-Tris(2,4-dihydroxyphenyl)-1,3,5- triazine, 2,4,6-Tris(4-butoxy-2-hydroxyphenyl)-1,3,5-triazine, 2,4-Bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, Bemotrizinol, and the like. Specific examples of the polymerizable triazine-based ultraviolet absorber include triazine methacrylate and triazine acrylate.

[0042] As the polymerizable ultraviolet absorber, benzotriazole-based ones are preferred. Benzotriazole-based ones have excellent ultraviolet absorption per mass, and can impart excellent ultraviolet resistance with a small amount. Among them, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (Otsuka Chemical Co., Ltd. "RUVA-93") is particularly preferred because of its excellent stability during emulsion polymerization.

[0043] (Weight average molecular weight of vinylidene chloride copolymer) The weight average molecular weight of the vinylidene chloride copolymer of this embodiment is preferably 300,000 or less, more preferably 200,000 or less, even more preferably 150,000 or less, and particularly preferably 120,000 or less. When the weight average molecular weight is within the above range, it means that the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment has been polymerized at a sufficient polymerization rate, and tends to have few blocks of structural units derived from vinylidene chloride and to have an excellent film-forming life. In addition, after film formation, the copolymer has a sufficient crystallization rate and tends to exhibit excellent barrier properties in a short time after coating. The weight-average molecular weight of the vinylidene chloride copolymer is preferably 60,000 or more, more preferably 80,000 or more. A vinylidene chloride copolymer having a low weight-average molecular weight tends to have a high crystallization rate. When the weight-average molecular weight is within the above range, the aqueous dispersion of the vinylidene chloride copolymer tends to have an excellent film-forming life. Here, the weight average molecular weight can be determined from a polystyrene standard calibration curve using gel permeation chromatography (GCP) under the following conditions. (Equipment): Prominence (manufactured by Shimadzu Corporation) (Device configuration) Liquid delivery unit: LC-20AD Degasser; DGC-20A Autosampler: SIL-20A HT Detector: RID-10A Column oven: CTO-20A Analyzer: LCsolution (Columns used): TSKgel GMHXL (manufactured by Tosoh Corporation) TSKgel G4000HXL (manufactured by Tosoh Corporation) (Carrier): Tetrahydrofuran (THF) (Detector): RI detector (Measurement temperature): 40℃ (Flow rate): 1.0mL / min (Sample concentration): 0.3% solution (Injection volume): 100μL When different analytical conditions such as columns and detectors are used, the molecular weight values ​​obtained may vary.

[0044] The average particle size of the vinylidene chloride copolymer particles contained in the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment is not particularly limited, but is preferably 10 to 1000 nm. When the average particle size is within this range, the storage stability of the aqueous dispersion tends to be good, and the coatability tends to be improved. The average particle size of the vinylidene chloride copolymer particles is more preferably 200 nm or less, even more preferably 180 nm or less, even more preferably 150 nm or less, and particularly preferably 140 nm or less. When the vinylidene chloride copolymer crystallizes, the film-forming life is shortened. Crystallization proceeds through the process of nucleation and nucleus growth, but in the state of the aqueous dispersion, the nuclei cannot grow beyond the particle size because they are restricted by the particle size. By reducing the average particle size, the size of each generated crystal nucleus that can be crystallized can be reduced, thereby suppressing crystallization of the entire aqueous dispersion, and extending the film-forming life. The average particle size of the vinylidene chloride copolymer particles is more preferably 100 nm or more, even more preferably 110 nm or more, and particularly preferably 120 nm or more. If the average particle size is too small, the viscosity of the aqueous dispersion increases, and it tends to be difficult to obtain a smooth coating film. An uneven coating film has poor barrier properties because gases pass through the thin parts of the film. In addition, an uneven coating film has poor transparency because the uneven surface scatters light. In addition, the yellowness index YI of a film having a layer formed by applying an aqueous dispersion of vinylidene chloride copolymer increases due to light scattering on the surface. By designing an aqueous dispersion so that the average particle size of the vinylidene chloride copolymer particles is within the above range, an aqueous dispersion that is easy to obtain a smooth coating film can be obtained. Here, the yellowness index YI can be determined using a color difference meter CM-5 manufactured by Konica Minolta, Inc., as described below.

[0045] The solid content of the aqueous dispersion of the vinylidene chloride copolymer of this embodiment is preferably 10% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, still more preferably more than 50%, and particularly preferably more than 58%. The higher the solid content, the higher the coating amount per coating, so the number of coatings required to obtain the target film thickness is reduced, and the productivity of the coated film is high. In addition, the time that the aqueous dispersion is exposed to heat during drying is shortened, and discoloration of the vinylidene chloride copolymer in the coating film due to decomposition can be suppressed. The solid content in the aqueous dispersion of the present embodiment refers to the proportion of the total mass of all solid components contained in the aqueous dispersion, and may be only the vinylidene chloride copolymer, or may contain a polymer compound other than the vinylidene chloride copolymer described below, a seed latex, and additives. When the solid content contains a mass proportion of components other than the vinylidene chloride copolymer, the mass proportion of the components other than the vinylidene chloride copolymer is preferably 7 mass % or less, taking the water dispersion as 100 mass %.

[0046] The solid content of the aqueous dispersion can be measured by the following method. <Solid content measurement> Weigh out 2.5 g of the aqueous dispersion into a CEM Smart System 5 solids meter, dry it at 20°C and 50% RH, and measure it. Average the results of three measurements and calculate the solids content using the formula (dry mass / aqueous dispersion mass) x 100.

[0047] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment preferably contains a crystal nucleating agent. The crystal nucleating agent is an additive that promotes crystallization of a film formed from the aqueous dispersion, and any known crystal nucleating agent that promotes crystallization of a resin can be used. Examples of such crystal nucleating agents include metal phosphates, metal benzoates, metal pimelates, metal rosin salts, benzylidene sorbitol, quinacridone, cyanine blue, metal oxalates, metal stearates, ionomers, high melting point PET, carbon black, metal oxides, metal sulfates, kaolin, clay, high melting point polyamides, crystalline resins having a different composition from the vinylidene chloride copolymer of the present embodiment described above, silica, titanium oxide, wax, highly crystalline vinylidene chloride polymer particles different from the vinylidene chloride copolymer of the present embodiment described above, and the like. It is also possible to use one or more of these in combination. Preferred are silica, titanium oxide, wax, and highly crystalline vinylidene chloride polymer particles, and particularly preferred are wax and highly crystalline vinylidene chloride polymer particles. The addition of these crystal nucleating agents promotes the progress of crystallization after film formation, and the coating film exhibits high water vapor barrier properties. The content of the crystal nucleating agent is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 2 parts by mass or less, based on 100 parts by mass of the vinylidene chloride copolymer. The content of the crystal nucleating agent is preferably more than 0 part by mass, and more preferably 0.05 part by mass or more. When multiple crystal nucleating agents are added, the total amount is used.

[0048] The term "wax" is understood herein to denote any natural or synthetic wax, including, but not limited to, hazel wax, urushi wax, sugar cane wax, palm wax, candelilla wax, jojoba oil, beeswax, spermaceti wax, ivory wax, wool wax, FT wax, paraffin wax, microwax, carnauba wax, beeswax, china wax, ozokerite, polyolefin wax and montan wax, and esters thereof.

[0049] (Polymer compounds other than vinylidene chloride copolymers) The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may contain a polymer compound other than the vinylidene chloride copolymer. When the total mass of the vinylidene chloride copolymer is 100 parts by mass, the content of the polymer compound other than the vinylidene chloride copolymer is 0 parts by mass or more and less than 20 parts by mass, preferably 0 parts by mass or more and less than 10 parts by mass, and more preferably 0 parts by mass or more and less than 5 parts by mass. If the content of the polymer compound other than the vinylidene chloride copolymer is 20 parts by mass or more, the gas barrier property is reduced, and the obtained coating film is whitened due to the difference in refractive index, and the visibility of the contents is poor when the coating film is used as a packaging material. By designing the content of the polymer compound other than the vinylidene chloride copolymer to be within the above range, an aqueous dispersion of the vinylidene chloride copolymer having excellent gas barrier property and transparency of the coating film can be obtained. In addition, the amount of the polymer compound other than the vinylidene chloride copolymer that has low solubility in a wide range of solvents increases, and the solubility to the outside of the film or paper when coated on the film or paper is deteriorated. In particular, the elution property in hydrophobic solvents deteriorates, which can be evaluated by the elution property in toluene described later. Here, "polymeric compound other than vinylidene chloride copolymer" refers to a polymeric compound in which the proportion of structural units derived from monomers other than vinylidene chloride is 50% by mass or more when the total mass of the polymeric compound is 100% by mass.

[0050] Monomers other than vinylidene chloride that are used as raw materials for polymer compounds other than vinylidene chloride copolymers are not particularly limited, and examples thereof include (meth)acrylic monomers such as methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, glycidyl acrylate, acrylonitrile, methacrylonitrile, acrylic acid, methacrylic acid, acrylamide, and N-methylol acrylamide; styrene, 2-sulfoethyl methacrylic acid (2-SEM) or a salt thereof (such as a sodium salt); a phosphate ester of methacrylate-terminated polypropylene glycol or a salt thereof (such as a sodium salt); and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) or a salt thereof (such as a sodium salt).

[0051] Furthermore, the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may contain, as necessary, various additives that are commonly used, for example, an oxidizing agent, an antifoaming agent, a rheology modifier, a thickener, a dispersant, a stabilizer such as a surfactant, a wetting agent, a plasticizer, a colorant, silicone oil, etc. Furthermore, the aqueous dispersion may also be used by blending, as necessary, a light stabilizer, a silane coupling agent, an inorganic filler, a color pigment, an extender pigment, an oxidizing agent, etc. The content of the oxidizing agent is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, based on 100 parts by mass of the vinylidene chloride copolymer. The addition of the oxidizing agent can suppress discoloration of the coating film of the aqueous dispersion. The oxidizing agent is preferably an oxygen-based bleaching agent, more preferably a peroxide (such as hydrogen peroxide), a persulfate, percarbonate, or peracetic acid, and even more preferably hydrogen peroxide. The solvent of the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may be water alone, or may contain water and other solvents (e.g., alcohols, acetone, etc.). When other solvents are contained, the amount of such solvents is preferably 10 parts by mass or less per 100 parts by mass of water.

[0052] [Maximum melting peak temperature and melting peak area of ​​vinylidene chloride copolymer aqueous dispersion] The maximum melting peak temperature (maximum melting point) and melting peak area of ​​the aqueous dispersion of the vinylidene chloride copolymer can be evaluated using a sample prepared by either of the following two methods (i) or (ii). The maximum melting peak temperature is preferably 170°C or lower, and particularly preferably 160°C or lower. In addition, when the area of ​​a melting peak having a melting peak temperature of 170°C or higher of an aqueous dispersion of the vinylidene chloride copolymer is S1 and the area of ​​a melting peak having a melting peak temperature of less than 170°C is S2, S1 / (S1+S2) is preferably 0 or more and 0.33 or less, particularly preferably 0.31 or less, and further preferably 0.26 or less. The more blocks of structural units derived from vinylidene chloride are formed in the vinylidene chloride copolymer, the greater the melting peak area at 170°C or higher. In an aqueous dispersion in which many blocks having structural units derived from vinylidene chloride are formed, poor film formation due to crystallization originating from the blocks is likely to occur during long-term storage. When S1 / (S1+S2) is within the above range, the copolymer has a small melting peak area at 170°C or higher, i.e., a copolymer with a small amount of blocks having a large amount of structural units derived from vinylidene chloride, and tends to have good film formability after long-term storage. The method for controlling the area of ​​the melting peak at 170° C. or higher is not particularly limited, and examples thereof include a method of suppressing accumulation of monomers by promoting the polymerization reaction through the addition of a polymerization activator that accelerates the radical decomposition of the initiator, and a method of reducing the amount of vinylidene chloride accumulated at the end of polymerization by reducing the proportion of vinylidene chloride in the raw material monomer.

[0053] (i) When an aqueous dispersion of a vinylidene chloride copolymer is available, this method is used. A water dispersion of vinylidene chloride copolymer was applied to an aluminum plate at a dry coating weight of 10 g / m 2The film is then coated with a Mayer bar so that the film becomes uniform, and dried in an oven maintained at 100°C for 1 minute. The dried film is peeled off with tweezers within 5 minutes to obtain a film of vinylidene chloride copolymer. 5 mg of the film is then taken and used for measurement. When an additive such as a crystal nucleating agent is added to the aqueous dispersion, a sample is prepared and measured using the aqueous dispersion to which the additive has been added. (ii) When an aqueous dispersion of a vinylidene chloride copolymer is not available and only a film or paper laminate having a vinylidene chloride copolymer layer is available, the following method is used. The vinylidene chloride copolymer (layer) is separated from the film having the vinylidene chloride copolymer layer, and 5 mg is sampled for measurement.

[0054] <Method for separating vinylidene chloride copolymer (layer) from film> As a method for separating a vinylidene chloride copolymer (layer) from a film having a vinylidene chloride copolymer layer, the following methods (A) to (C) are used when possible. When (A) is possible, use (A); when (A) is difficult and (B) is possible, use (B); when (A) and (B) are difficult and (C) is possible, use (C). (A) Physically peel off or scrape off with tweezers or other tools. (B) The vinylidene chloride copolymer does not dissolve, but is chemically separated by using a solvent that dissolves the primer, preferably acetone. (C) The vinylidene chloride copolymer is dissolved in a solvent that dissolves nothing other than the vinylidene chloride copolymer, and the vinylidene chloride copolymer is eluted and separated by drying. When separation is performed using a solvent by method (B) or (C), the vinylidene chloride copolymer is dried in a drying oven or the like to the extent that the vinylidene chloride copolymer is not decomposed, and the measurement is performed after confirming that the mass of the solvent in the separated product is 0.5 mass% or less. The drying conditions are a temperature of 50°C or less, a drying time of 10 hours or less, and, if necessary, under reduced pressure. If any of (A) to (C) is difficult and other separable means are available, those may be used. It is preferable to wash and dry the separated product so that the content of impurities other than the vinylidene chloride copolymer in the separated product is as small as possible. The mass ratio of the above impurities in the measurement sample is preferably 0.5 mass% or less. The drying treatment conditions are a temperature of 60°C or less and a treatment time of 10 hours or less. Here, impurities refer to components that are not included in the aqueous dispersion of vinylidene chloride copolymer before coating, such as mixed primers and solvents, and do not include additives such as emulsifiers that are added to the aqueous dispersion from the beginning. The amount of emulsifier in the separated product can be measured by the following procedure. i) The mass of the dried separated product is designated as W1. ii) The separated product is washed with a large amount of pure water that is at least 50 times the mass W1. At this time, care is taken not to let the vinylidene chloride copolymer flow out together with the washed separated product. iii) The washed separated product is dried, and its mass is designated as W2. iv) The mass of the emulsifier is calculated by W1 - W2.

[0055] The sample collected by the above method is heated to 170°C at 10°C / min under a nitrogen atmosphere using a TA Instruments Q-2000 differential scanning calorimeter, and cooled to -40°C at 10°C / min. It is then heated to 190°C at 10°C / min, and measurement data is obtained up to 190°C. Of the measurement data obtained up to 190°C, data above 180°C is not used because vinylidene chloride begins to decompose above 180°C, and the maximum melting peak temperature is determined using the measurement values ​​from -40°C to 180°C during the second heating.

[0056] In this measurement, for example, an aluminum Tzero Pan and Tzero hermetic lid (manufactured by TA Instruments) are used as a sample pan, and an empty pan is used as a reference. In other words, the maximum melting peak temperature is calculated based on the value obtained by subtracting the empty pan measurement result from the sample measurement result.

[0057] 1q Next, a baseline is drawn using the method described below, and the area of ​​the melting peak below 170°C is calculated using Integrate Peak Linear in the Q-2000 analysis tool TA Universal Analysis, and this is designated as S2. If there is no melting peak below 170°C, S2 is designated as 0.

[0058] Draw a baseline using the method described below, and calculate the area of ​​the melting peak above 170°C using Integrate Peak Linear in the Q-2000 analysis tool TA Universal Analysis, and call this S1. If there is no melting peak above 170°C, S1 is set to 0. The calculated values ​​of S1 and S2 are rounded off to one decimal place.

[0059] There are cases where the baselines are not collinear, examples of which are given in Inorganic Materials, vol. 3, Jul. 271-283 (1996).

[0060] Here are some examples of how to draw the baseline. If there are multiple peaks, draw a baseline for each peak and calculate the area. In the following cases, if multiple tangents can be drawn, the one with the largest absolute value of the slope is used as the tangent to the curve.

[0061] (I): When a single tangent line can be drawn that touches both the positive and negative curves across the peak, the tangent line that touches both the positive and negative curves is used as the baseline. (II): In cases not falling under (I) and in which the peak is sandwiched between lines parallel to the horizontal axis on both the positive and negative sides of the peak, the baseline shall be the line connecting the points on either side of the peak where the endothermic peaks on the positive and negative sides are no longer parallel to the horizontal axis (points where they slope positively or negatively). (III): If the case does not fall under (I) or (II) and one of the positive or negative sides of the peak is a line parallel to the horizontal axis and the other is a curve, the point where the line parallel to the horizontal axis no longer is taken as the starting point, and a tangent line is drawn to the other curve side to form the baseline. (IV): If the case does not fall under any of (I), (II), or (III) and the positive side of the peak is cut off by the upper measurement limit of 180° C., the point at 180° C. is taken as the starting point, and a tangent line is drawn on the negative side of the peak as the baseline. If the negative side of the peak is a line parallel to the horizontal axis, the line connecting the above starting point and the point where it is no longer parallel to the horizontal axis may be taken as the baseline.

[0062] [Surface tension of aqueous dispersion of vinylidene chloride copolymer] The surface tension of the aqueous dispersion of the vinylidene chloride copolymer of this embodiment is preferably less than 48 mN / m, and particularly preferably less than 45 mN / m. An aqueous dispersion having a surface tension in this range tends to have excellent stability during long-term storage. In addition, since the aqueous dispersion also tends to have excellent stability under high-speed shear, high-speed coating is possible, and the productivity during coating is high. In addition, due to excellent wettability, a smooth coating film is easily obtained even during high-speed coating. A coating film that is not smooth has poor barrier properties because gas permeates through the thin film thickness. In addition, a coating film that is not smooth has poor transparency because the uneven surface scatters light. In addition, the yellowness index YI of a film having a layer formed from a vinylidene chloride copolymer increases due to light scattering on the surface. Here, the yellowness index YI can be determined using a color difference meter CM-5 manufactured by Konica Minolta, Inc., as described below. The surface tension of the aqueous dispersion of this embodiment is preferably 20 mN / m or more, more preferably 30 mN / m or more, even more preferably 35 mN / m or more, and particularly preferably 40 mN / m or more. When the surface tension is within this range, poor appearance due to low surface tension is suppressed, and the aqueous dispersion can provide a film with excellent transparency and appearance. Here, the surface tension can be measured using a fully automatic surface tensiometer CBVP-Z (manufactured by Kyowa Interface Science Co., Ltd.) by the platinum plate method in an environment of 20° C. and 50% Rh.

[0063] [Method of producing aqueous dispersion of vinylidene chloride copolymer] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be produced by emulsion polymerization of a mixture of raw material monomers for the vinylidene chloride copolymer. Although not particularly limited, the emulsion polymerization is usually carried out at a temperature of 30 to 70°C. The polymerization temperature is preferably within a range of 40 to 60°C. By setting the polymerization temperature at 70°C or less, decomposition of the raw materials during polymerization can be suppressed, which is preferable. By setting the polymerization temperature at 30°C or more, the polymerization rate can be increased, which improves the efficiency of polymerization, which is preferable.

[0064] When carrying out the emulsion polymerization of vinylidene chloride, an aqueous dispersion synthesized from raw material monomers having different monomer compositions synthesized in the same or another polymerization machine may be added as a seed latex as a raw material.Preferably, it is an aqueous dispersion obtained by emulsion polymerization of an acrylic monomer or a methacrylic monomer, more preferably, an aqueous dispersion of a homopolymer or copolymer of methyl methacrylate or a copolymer of glycidyl methacrylate, and even more preferably, the proportion of constituent units derived from methyl methacrylate is 80 parts by mass or more when the total amount of monomer units constituting the seed is 100 parts by mass. The addition of seed latex increases the polymerization rate and is expected to improve the film-forming life of the product. In particular, when the ratio of the constituent units derived from methyl methacrylate is 80 parts by mass or more when the total amount of the monomer units constituting the seed is 100 parts by mass, the latex has excellent aggregation stability. This is because methyl methacrylate-based seeds have a high glass transition temperature. Furthermore, when the polymerizable ultraviolet absorber is copolymerized with vinylidene chloride, there is an advantage that the polymerization residue derived from the unreacted polymerizable ultraviolet absorber is reduced. The benzotriazole, triazine, and benzophenone moieties of the polymerizable ultraviolet absorber are very hydrophobic, and if they are introduced into a polymerization machine in which there is no sufficient reaction field, they will precipitate and become polymerization residue. On the other hand, when a seed is used, the seed acts as a reaction field, and the ultraviolet absorber is efficiently introduced into the seed particle, so that polymerization residue is less likely to occur. In particular, when the ratio of the constituent unit derived from methyl methacrylate is 80 parts by mass or more when the total amount of the monomer units constituting the seed is 100 parts by mass, the polymerizable ultraviolet absorber easily penetrates into the seed particle, and the effect of reducing the residue is large. The amount of the seed latex added is preferably 0.5 parts by mass or more, more preferably 1.2 parts by mass or more, and even more preferably 3.0 parts by mass or more, based on 100 parts by mass of the vinylidene chloride copolymer. The amount of the seed latex added is preferably 10 parts by mass or less, more preferably 5.0 parts by mass or less, and even more preferably 4.0 parts by mass or less. The seed latex is preferably added before the start of polymerization of vinylidene chloride, but the seed latex may be added continuously in parallel with the continuous addition of the monomer.

[0065] After the emulsion polymerization of the aqueous dispersion of the vinylidene chloride copolymer is completed, additional polymerization may be carried out by adding raw material monomers having a different monomer composition to the aqueous dispersion in the same or another polymerization machine. This allows the polymer formed by polymerization of the newly added monomers to form a structure that coats the vinylidene chloride copolymer particles, and is expected to improve the film formation life and the mechanical properties of the film. The amount of the polymer formed by the additional polymerization is preferably 10 parts by mass or less based on 100 parts by mass of the vinylidene chloride copolymer.

[0066] Examples of surfactants that can be used in the emulsion polymerization of the aqueous dispersion of the vinylidene chloride copolymer include anionic surfactants such as alkyl sulfate salts, alkyl benzene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, and alkyl sulfonates.

[0067] Examples of the polymerization initiator include persulfates such as sodium persulfate and potassium persulfate, and peroxides such as hydrogen peroxide, t-butyl hydroperoxide and cumene hydroperoxide, with t-butyl hydroperoxide being preferred.

[0068] As a polymerization activator, it is preferable to add a polymerization activator that accelerates the radical decomposition of the initiator, such as sodium hydrogen sulfite or sodium D-araboascorbate. These polymerization activators are preferably added to promote the decomposition of the polymerization initiator. However, on the other hand, in order to promote the decomposition of the oxidizing agent, the amount of addition is preferably as small as possible within the range required for radical decomposition of the polymerization initiator.

[0069] These polymerization additives are not particularly limited, and may be, for example, of the type that has been conventionally and preferably used in this technical field.

[0070] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be used as a coating material for films used for blister packages, food packages, protection of electronic parts, and the like.

[0071] [film] The film of the present embodiment is a film produced by coating an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above, i.e., a multilayer film having a vinylidene chloride copolymer layer coated with an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above.

[0072] The film of the present embodiment preferably has a layer formed by applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment onto a film substrate. The film substrate is not particularly limited, but representative examples include films made of polyvinyl chloride, polyester, polyamide, polypropylene, polyethylene, cyclic polyolefin, and cellophane. In the case of blister packaging, a film made of polyvinyl chloride is used. The thickness of the film substrate varies depending on the material used, but may usually be 8 to 300 μm. The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can impart not only gas barrier properties but also ultraviolet absorbing properties to the film, and is therefore particularly useful when it is difficult to add an ultraviolet absorber to the substrate. In general, cases in which it is difficult to add an ultraviolet absorber to the substrate include cases where it is difficult to add the ultraviolet absorber due to the manufacturing process, such as cellophane, and cases in which the migration of additives to the contents is particularly limited, such as pharmaceutical packaging.

[0073] In addition, the film of the present embodiment may optionally include a layer of a copolymer functionally adjusted mainly with a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer. An example of such a layer is a primer layer formed on a film substrate using an aqueous resin emulsion or an acrylic dispersion, and the vinylidene chloride copolymer layer may be provided thereon by applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above.

[0074] The film of the present embodiment may optionally further include at least one layer of a vinylidene chloride copolymer having chemical or physical properties different from those of the vinylidene chloride copolymer of the present embodiment, for example, a film in which an aqueous dispersion of a vinylidene chloride copolymer having a different composition is applied onto the vinylidene chloride copolymer layer of the present embodiment for the purpose of preventing blocking or improving the slipping property of the film. Another example is a film in which layers of the vinylidene chloride copolymer of the present embodiment and layers of a vinylidene chloride copolymer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A film having this structure is expected to have high impact resistance. In the case of a film having layers of a plurality of kinds of vinylidene chloride copolymers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers.

[0075] The outermost surface of the film of this embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer formed by coating the vinylidene chloride copolymer of this embodiment. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer of this embodiment, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the film is used as a packaging material.

[0076] The film of this embodiment has a vinylidene chloride copolymer layer containing an ultraviolet absorber (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer) formed by applying an aqueous dispersion of the vinylidene chloride copolymer of this embodiment. It is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorber. Such a film has excellent recyclability because the film base can be recovered in a state free of ultraviolet absorbers by separating the vinylidene chloride copolymer layer containing an ultraviolet absorber. In addition, when used as a packaging material, the layer not containing an ultraviolet absorber can be made to be a layer in contact with the contents, thereby preventing the ultraviolet absorber from migrating to the contents. Any method can be used to determine whether each layer contains an ultraviolet absorber, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether the vinylidene chloride copolymer layer is a layer formed by applying the aqueous dispersion of the present embodiment or obtained by another method. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether the layer contains an emulsifier, and if it contains an emulsifier, it can be said that the layer is formed by applying the aqueous dispersion of the present embodiment.

[0077] Whether each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the collected layer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the addition. Note that vinylidene chloride copolymer is hydrophobic, so it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when the film is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.

[0078] The coating mass of the vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the vinylidene chloride copolymer after drying is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 By increasing the coating weight after drying, the gas barrier properties of the entire film can be improved. In order to increase the coating weight, a method of repeatedly coating the aqueous dispersion is generally used. When the number of times of coating is increased, it becomes difficult to obtain a uniform coating film because the aqueous dispersion is repeatedly coated on the film with cracks in the aqueous dispersion whose film-forming property has deteriorated due to long-term storage. For this reason, the aqueous dispersion of vinylidene chloride copolymer having improved film-forming life according to the present embodiment is very useful in producing a film with a large final coating weight.

[0079] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment is preferably applied to a film substrate as exemplified above and used as a blister package. The obtained blister package exhibits excellent water vapor barrier properties and ultraviolet light absorption properties. Furthermore, in addition to being applied to blister packages, the film of this embodiment can also be used as it is as a coating agent to form a clear film.

[0080] As a method for applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment to the surface of the substrate, a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc. Usually, after the aqueous dispersion is applied to the film substrate, the film is dried by keeping it at room temperature or under heating for a predetermined time.

[0081] Hereinafter, a method for estimating the absorption coefficient ε1 of the vinylidene chloride copolymer (PVDC layer) at a wavelength of 360 nm from a film having a vinylidene chloride copolymer (PVDC) layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer of this embodiment will be described.

[0082] First, the method for calculating the absorption coefficient ε4 of the film at a wavelength of 360 nm will be explained below. The film is used as a measurement sample, and the absorbance A at a wavelength of 360 nm is 360all Separately, the absorbance at a wavelength of 360 nm of each layer other than the PVDC layer is measured separately, and the absorbances A1, A2, ... A of each layer at a wavelength of 360 nm are measured. i (i is the layer number). Absorbance A of PVDC layer at 360 nm 360PVDC can be calculated using the following formula (1). A 360PVDC =A 360all -Σ(A j ) ···(1) (In the formula, j represents an integer from 1 to i.) Obtained A 360PVDC By substituting the thickness d [cm] of the PVDC layer into the Beer-Lambert equation below, the absorption coefficient of the film ε4 [cm -1 ] can be obtained. Beer-Lambert formula: A 360PVDC = ε4×d Here, the thickness d of the PVDC layer is determined by subtracting the thicknesses of the layers other than the PVDC layer from the total thickness of the film. Most accurately, the thickness of the PVDC layer is measured by observing the cross section of the film in the thickness direction using a SEM or the like.

[0083] A 360PVDC As is clear from the calculation formula (1), A 360PVDC Must be A 360all is smaller than A. 360all and the thickness d of the PVDC layer is calculated using the Beer-Lambert equation (A 360all = ε360max × d), ε4 is smaller than the absorption coefficient ε360max obtained by substituting

[0084] Next, we will explain the relationship between the absorption coefficient ε4 of the film at a wavelength of 360 nm and the absorption coefficient ε1 of the PVDC layer. ε4 is affected by the drying conditions and the substrate. However, since the absorption coefficient at a wavelength of 360 nm is dominated by the ultraviolet absorbing substance, it is possible to obtain a converted ε4 with a value close to ε1 by converting the units of ε4. The conversion formula is as follows: Conversion ε4 = ε4 / (1000 × density of PVDC layer) The density of the PVDC layer [g / cm 3 ] can be measured using a dry density meter using helium gas. The conversions ε4 and ε1 are essentially close in meaning, and if the conversion ε4 is within the range described above for ε1, then it is highly likely that ε1 is also within the range.

[0085] [Paper laminate] The paper laminate of this embodiment is a coated paper prepared by coating with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above, i.e., a multi-layer paper having a vinylidene chloride copolymer layer coated with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above. The paper laminate of this embodiment can be used as moisture-proof paper.

[0086] The paper laminate of this embodiment preferably has a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer of this embodiment on a paper base material. The paper base material of the present embodiment is preferably composed of pulp and a filler, and may contain various chemicals as necessary. The paper base material is preferably in the form of a sheet. Examples of the paper base material in this embodiment include various well-known papers such as fine paper, medium quality paper, coated paper, one-side glossy paper, kraft paper, one-side glossy kraft paper, bleached kraft paper, glassine paper, paperboard, white paperboard, and liner.

[0087] The pulp constituting the paper base material may be chemical pulp such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, etc., mechanical pulp such as stone grind pulp and thermomechanical pulp, wood fibers such as deinked pulp and waste paper pulp, non-wood fibers obtained from kenaf, bamboo, hemp, etc., and these may be used in appropriate combinations. Among these, it is preferable to use wood fiber pulp, chemical pulp, and mechanical pulp, and it is more preferable to use chemical pulp, because foreign matter is less likely to be mixed into the base paper, discoloration is less likely to occur over time when the laminate (packaging container) after use is used as a waste paper raw material for recycling, the surface texture is good when printed due to its high whiteness, and the value of use is high, especially when used as a packaging material.

[0088] The average fiber length of the pulp fibers constituting the paper base material is preferably 5 mm or less, and the average fiber width is preferably 100 μm or less. The fiber length and fiber width of the pulp fibers affect the size of the capillaries formed in the gaps between the pulp fibers in the paper base material, and the smaller the fiber length and fiber width of the pulp fibers, the smaller the capillaries, and the more suppressed the absorption of the aqueous dispersion of the vinylidene chloride copolymer into the paper base material. Furthermore, since the mechanical strength of the paper base material is increased, the coating speed of the aqueous dispersion can be increased, and it is also easy to mold the paper base material into a packaging container, etc. The average fiber length of the pulp fibers is more preferably 4 mm or less, further preferably 3 mm or less, and particularly preferably 2 mm or less. There is no particular lower limit, but in order to obtain an appropriate mechanical strength, it is preferably 1 mm or more. The average fiber width of the pulp fibers is more preferably 50 μm or less, further preferably 40 μm or less, and particularly preferably 30 μm or less. Although there is no particular lower limit, in order to obtain an appropriate mechanical strength, it is preferably 10 μm or more. The average fiber length and average fiber width of pulp fibers are measured by the following method. Ion-exchanged water and paper base material are weighed out so that the paper base material is 0.1 mass % and the total amount is 300 g, and a high-shear homogenizer (for example, Nippon Seiki Co., Ltd., product name "Excel Auto Homogenizer ED-7") is used to perform a fiberization process (15,000 rpm x 5 minutes) to form a slurry. The obtained slurry is cast on mica, air-dried, and measured with a high-resolution scanning electron microscope (SEM). In the particle image obtained during the measurement, the major axis (L) and minor axis (D) of 100 to 150 arbitrarily selected particles are measured, and the average values ​​of these are taken as the average fiber length and average fiber width, respectively.

[0089] As the filler constituting the paper base material, known fillers such as white carbon, talc, kaolin, clay, calcium bicarbonate, light calcium carbonate, titanium oxide, zeolite, and synthetic resin fillers can be used.

[0090] Furthermore, in order to improve adhesion between the vinylidene chloride copolymer and the paper base material and retention, the paper base material may contain various chemicals or may be surface-treated with various chemicals, such as sizing agents, water-resistant agents, and paper strength agents.

[0091] Examples of the sizing agent include styrene-based sizing agents, alkyl ketene dimers (AKD), alkenyl succinic anhydrides (ASA), neutral rosin sizing agents, rosin sizing agents, modified rosin emulsion sizing agents, etc. Among these, rosin sizing agents and modified rosin emulsion sizing agents are preferred. The rosin sizing agent may be one that has been conventionally known in the papermaking field, and is not particularly limited. Examples of rosin-based substances include reinforced rosins obtained by modifying rosins such as gum rosin, wood rosin, and tall oil rosin with α,β-unsaturated carboxylic acids such as fumaric acid, maleic acid, and acrylic acid or their anhydrides, and rosin esters obtained by reacting the above rosins with polyhydric alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and diglycerin. The rosin sizing agent also includes emulsions of these alone or a mixture of these, and emulsions of each alone and then mixed. Furthermore, the above emulsions also include those to which various polymers have been added in order to further improve sizing properties. The content of the sizing agent in the paper base material is preferably 0.1 to 10 kg / t in terms of solid content. When the content of the sizing agent is within the above range, water absorption and repelling into the paper base material can be suppressed when the aqueous dispersion of vinylidene chloride copolymer particles is applied.

[0092] Examples of the water-resistant agent include melamine formaldehyde resins having a methylol group, an aldehyde group, an epoxy group, etc., glyoxal resins, polyamide epoxy resins, and ammonium zirconium carbonate. The content of the waterproofing agent in the paper base material is preferably 0.02 to 3 parts by mass per 100 parts by mass of pulp. When the content of the waterproofing agent is within the above range, excellent initial adhesive strength can be obtained.

[0093] The paper base material may also contain a paper strength enhancer to impart strength. As the paper strength enhancer, various known ones such as polyacrylamide resin, polyamide resin, polyamine resin, acrylic resin, melamine resin, urea resin, polyamide epichlorohydrin resin, etc. can be used. Among these, it is preferable to use an amphoteric paper strength enhancer, and amphoteric polyacrylamide is particularly preferable. Amphoteric polyacrylamides include acrylamide and anionic monomers (unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, 2-(meth)acrylamido-N-glycolic acid, and N-acryloylglycine; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid; unsaturated tricarboxylic acids such as aconitic acid and 3-butene-1,2,3-tricarboxylic acid; unsaturated tetracarboxylic acids such as 1-pentene-1,1,4,4-tetracarboxylic acid, 4-pentene-1,2,3,4-tetracarboxylic acid, and 3-hexene-1,1,6,6-tetracarboxylic acid; unsaturated sulfonic acids such as vinyl sulfonic acid, styrene sulfonic acid, and 2-acrylamido-2-methylpropane sulfonic acid). unsaturated phosphonic acids such as vinylphosphonic acid and α-phenylvinylphosphonic acid; alkali metal salts such as sodium and potassium salts or ammonium salts of the above-mentioned anionic vinyl monomers) and cationic monomers (dimethylaminoethyl methacrylate, diallyldimethylammonium chloride, diallyldiethylammonium chloride, methacryloyloxyethyltrimethylammonium methyl sulfate, methacryloyloxyethyltrimethylammonium methyl chloride, methacrylamidepropyltrimethylammonium chloride, etc.), Mannich modified products and Hoffman decomposition products of copolymers of acrylamide and the above-mentioned anionic monomers. Since amphoteric polyacrylamide has a self-fixing function, even if the amount is increased to improve inter-paper strength, the amount of cations does not become excessive, and the modified rosin emulsion sizing agent can be stably fixed. The content of the paper strength enhancer in the paper base material is preferably 12 kg / t or more and 20 kg / t or less in terms of solid content. By setting the content of the paper strength enhancer in the above range, various paper strengths such as interlaminar strength can be imparted. If the content of the paper strength enhancer is below the above range, the interlaminar strength may be insufficient. On the other hand, if the content of the paper strength enhancer exceeds the above range, the improvement of the interlaminar strength will remain almost flat, and further, the retention of the added paper strength enhancer will decrease, causing stains and foaming in the papermaking machine system, which may decrease the operability. Therefore, aluminum sulfate and various anionic, nonionic, or amphoteric retention improvers, drainage improvers, and internal additives for papermaking may be used as necessary.

[0094] Furthermore, the paper base material may contain additives such as dyes, fluorescent whitening agents, pH adjusters, defoamers, pitch control agents, slime control agents, etc. as necessary. These agents may be conventionally known in the papermaking field and are not particularly limited. The content of these additives in the paper base material is preferably 500 kg / t or less in terms of solid content.

[0095] The basis weight of the paper base material is preferably 200 g / m from the viewpoint of flexibility for use in packaging applications such as packaging materials for food and medicine, containers, cups, etc. 2 Less than 100 g / m 2 Less than 80 g / m 2 Below 70 g / m 2 The lower limit is not particularly set, but the preferred range is 10 g / m 2 That's all.

[0096] The paper substrate may be a single layer, or may be made up of two or more layers.

[0097] The paper laminate of this embodiment may optionally further include a layer of at least one type of vinylidene chloride copolymer having chemical or physical properties different from those of the vinylidene chloride copolymer of this embodiment. For example, there may be mentioned a paper laminate in which an aqueous dispersion of a vinylidene chloride copolymer having a different composition is applied onto a layer coated with an aqueous dispersion of the vinylidene chloride copolymer of this embodiment for the purpose of preventing blocking or improving the slipperiness of the paper laminate. Another example is a paper laminate in which layers of the vinylidene chloride copolymer of the present embodiment and layers of a vinylidene chloride copolymer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A paper laminate having this structure is expected to have high impact resistance. In the case of such a paper laminate having layers of multiple types of vinylidene chloride copolymers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers.

[0098] The outermost surface of the paper laminate of this embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer coated with the vinylidene chloride copolymer of this embodiment. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer of this embodiment, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the paper laminate is used as a packaging material.

[0099] The coating mass of the vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the vinylidene chloride copolymer after drying is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 By increasing the coating film mass after drying, the water vapor barrier properties of the entire paper laminate can be improved. However, the thicker the vinylidene chloride copolymer layer, the smaller the discoloration degree of the vinylidene chloride copolymer layer per unit volume when viewed as a single sheet of paper laminate, but the larger the discoloration degree appears when rolled up. Thus, the thicker the vinylidene chloride copolymer layer of the paper laminate, the greater the effect of the vinylidene chloride copolymer of this embodiment in suppressing yellowing in the rolled state.

[0100] Furthermore, the paper laminate of this embodiment may optionally include a layer of a copolymer functionally adjusted mainly with a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer. Such a layer may be, for example, a primer layer formed on a paper substrate using an aqueous resin emulsion or an acrylic dispersion, on which the vinylidene chloride copolymer layer may be provided by applying the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above.

[0101] The paper laminate of this embodiment has a vinylidene chloride copolymer layer containing an ultraviolet absorber (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer) coated with an aqueous dispersion of the vinylidene chloride copolymer of this embodiment. It is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorber. Such a paper laminate has excellent recyclability because the paper base material can be recovered in a state free of ultraviolet absorbers by separating the vinylidene chloride copolymer layer containing an ultraviolet absorber. In addition, when used as a packaging material, the layer not containing an ultraviolet absorber can be made to be the layer in contact with the contents, thereby preventing the ultraviolet absorber from migrating to the contents. Any method can be used to determine whether each layer has an ultraviolet absorber or not, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether the vinylidene chloride copolymer layer is a layer formed by applying the aqueous dispersion of the present embodiment or obtained by another method. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether the layer contains an emulsifier, and if it contains an emulsifier, it can be said that the layer is formed by applying the aqueous dispersion of the present embodiment.

[0102] Whether each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the collected layer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the addition. Note that vinylidene chloride copolymer is hydrophobic, so it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber into the contents when the paper laminate is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the UV absorbent may migrate, which may reduce the UV absorbency of the paper laminate, so it is preferable to design it within the above range.

[0103] When the aqueous dispersion of the vinylidene chloride copolymer of this embodiment is applied to transparent paper, such as glassine paper, a paper material having gas barrier properties and ultraviolet absorbing properties can be produced. In recent years, paper packaging has been attracting attention due to the increasing need to reduce the amount of plastic. Since paper does not usually have gas barrier properties, a polyvinylidene chloride copolymer layer, an ethylene-vinyl alcohol copolymer layer, a polyvinyl alcohol layer, or the like is applied to a paper substrate in order to impart gas barrier properties. The ethylene-vinyl alcohol copolymer layer and the polyvinyl alcohol layer have high oxygen barrier properties but low water vapor barrier properties. On the other hand, the polyvinylidene chloride copolymer layer has both high oxygen barrier properties and water vapor barrier properties, and is excellent in that it can block oxygen and water vapor alone. In addition, since the monomer is synthesized using salt as a raw material, it is also excellent in that the amount of petroleum used is much less than other materials. Although paper has a drawback in that it discolors and deteriorates due to ultraviolet light, the paper laminate having a vinylidene chloride copolymer layer coated with the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment suppresses ultraviolet deterioration of the paper because the vinylidene chloride copolymer layer has ultraviolet absorbing properties, and furthermore, when used as a packaging material, ultraviolet deterioration of the contents can also be prevented. In the case of a resin-based film, it is possible to prevent deterioration to some extent by introducing an ultraviolet absorber into the film, but in the case of paper, it is difficult or disadvantageous in terms of cost to introduce an ultraviolet absorber into the paper. Therefore, in general, when imparting ultraviolet absorption, it is necessary to provide an ultraviolet absorbing layer separately from a gas barrier layer, but the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can form a vinylidene chloride copolymer layer that has oxygen barrier properties, water vapor barrier properties, and ultraviolet absorbing properties by simply coating it alone, and it is possible to block oxygen, water vapor, and ultraviolet rays all at once.

[0104] As a method for applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment to the paper substrate, a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc., can be used for the surface of the substrate. After application to the paper substrate, the coating is usually dried by keeping it at room temperature or under heating for a predetermined time.

[0105] (Surface tension of water dispersion) The surface tension of the aqueous dispersion of the vinylidene chloride copolymer of this embodiment is preferably less than 48 mN / m, and particularly preferably less than 45 mN / m. An aqueous dispersion having a surface tension in this range tends to have excellent stability during long-term storage. In addition, since the aqueous dispersion also tends to have excellent stability under high-speed shear, high-speed coating is possible, and the productivity during coating is high. In addition, due to excellent wettability, a smooth coating film is easily obtained even during high-speed coating. A coating film that is not smooth has poor barrier properties because gas permeates through the thin film thickness. In addition, a coating film that is not smooth has poor transparency because the uneven surface scatters light. In addition, the yellowness index YI of a film having a layer formed from a vinylidene chloride copolymer increases due to light scattering on the surface. Here, the yellowness index YI can be determined using a color difference meter CM-5 manufactured by Konica Minolta, Inc., as described below. The surface tension of the aqueous dispersion of this embodiment is preferably 20 mN / m or more, more preferably 30 mN / m or more, even more preferably 35 mN / m or more, and particularly preferably 40 mN / m or more. When the surface tension is within this range, poor appearance due to low surface tension is suppressed, and the aqueous dispersion can provide a film with excellent transparency and appearance. Here, the surface tension can be measured using a fully automatic surface tensiometer CBVP-Z (manufactured by Kyowa Interface Science Co., Ltd.) by the platinum plate method in an environment of 20° C. and 50% Rh.

[0106] The items (1) to (8) can be evaluated for the aqueous dispersion of the vinylidene chloride copolymer of the first aspect of this embodiment, the film or paper laminate having a vinylidene chloride copolymer layer coated with this aqueous dispersion, the film of the second aspect, and the paper laminate of the third aspect described below.

[0107] (1) Water vapor barrier properties The water vapor barrier property of a film having a layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be evaluated under conditions of 38°C and 100% RH using a water vapor transmission rate measuring device PERMATRAN 3 / 33 manufactured by MOCON (unit: g / m 2 ·day). However, the water vapor permeability is the average value measured between 48 hours and 60 hours after the start of the measurement. The measurement is carried out four times and the average value is used. Although not particularly limited, a film having a layer formed by applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be used in applications requiring high barrier properties (e.g., water vapor barrier properties), and the preferred range of water vapor permeability is 0.6 g / (m 2 ·day) or less, more preferably 0.5g / (m 2 ·day) or less, and more preferably 0.4 g / (m 2 ·day) or less.

[0108] (2) Film forming properties after long-term storage (film forming life) In a constant temperature and humidity room with an air temperature of 23°C and a humidity of 55%, 45 mL of the aqueous dispersion is taken into a 50 mL sample bottle, the lid is closed, and the bottle is left to stand for 5 hours. Next, in the constant temperature and humidity room, a thermal gradient tester (BIG HEART) manufactured by Imoto Manufacturing Co., Ltd. is adjusted to 10°C at one end and 30°C at the other end, and after confirming that the thermal gradient on the tester is 1°C per 4 cm, the aqueous dispersion is applied to the tester with a 0.2 mm applicator, dried for 12 hours, and the highest temperature at which cracks of 1 mm or more in diameter appear on the coating is taken as the minimum film formation temperature (MFT). The MFT is measured 10 times for one sample, and the average value is used. The prepared aqueous dispersion is stored at 23°C, and the MFT is measured every month. If the MFT at 0 months is TO and the MFT at n months is Tn, the change in MFT, ΔMFT, is calculated from Tn-TO. When ΔMFT≧4°C is satisfied, it is considered that the film-formability is impaired, and the first time ΔMFT≧4°C is satisfied is regarded as the limit of film-formability after long-term storage (film-forming life). For example, if the MFT is 12° C. in the 0th month, 13° C. in the 1st month, and 16° C. in the 2nd month, the film-forming life of the aqueous dispersion is 2 months. After this film formation life, it is no longer possible to obtain a uniform coating film, and the coating film is no longer able to exhibit sufficient water vapor barrier properties. Since an aqueous dispersion having a short film-forming life is difficult to distribute and store, the longer the film-forming life, the more desirable. In general, when distributing and storing an aqueous dispersion, the film-forming life is preferably 6 months or more, more preferably 7 months or more, even more preferably 8 months or more, and even more preferably 9 months or more.

[0109] The MFT (T0) of the aqueous dispersion of the vinylidene chloride copolymer immediately after synthesis (0th month) is preferably 25° C. or lower, more preferably 20° C. or lower. The lower the MFT, the better the film-forming property at low temperatures. In order to avoid thermal decomposition of the vinylidene chloride copolymer, the aqueous dispersion of this embodiment is preferably dried at a low temperature (preferably 80° C. or lower) within a range in which a coating film having good barrier properties can be obtained, but by lowering the MFT, it becomes possible to set the drying temperature low. The MFT (T0) of the aqueous dispersion of the vinylidene chloride copolymer immediately after synthesis (0th month) is preferably 10° C. or higher, and more preferably 15° C. or higher. When the MFT (T0) is in this range, an increase in the MFT during storage tends to be suppressed.

[0110] With respect to the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment and a film or paper laminate having a vinylidene chloride copolymer layer coated with this aqueous dispersion, the ultraviolet resistance and the elution of the ultraviolet absorber can be evaluated using the following parameters (3) and (4).

[0111] (3) UV resistance The ultraviolet resistance is a parameter that indicates the resistance to discoloration when the vinylidene chloride copolymer is irradiated with ultraviolet light. If the vinylidene chloride copolymer layer is discolored by ultraviolet light, the appearance of the film or paper laminate is impaired, so it is preferable that the ultraviolet resistance is high. Generally, vinylidene chloride copolymers are prone to discoloration to yellow when irradiated with ultraviolet light, but the vinylidene chloride copolymer having ultraviolet absorbing properties of the present embodiment has high ultraviolet resistance. (Preparation of measurement samples) A water dispersion of vinylidene chloride copolymer was applied to aluminum foil at a dry coating weight of 10 g / m 2 The coating is applied with a Mayer bar so that the coating becomes uniform, and then dried in an oven maintained at 100°C for 1 minute. The dried coating is peeled off with tweezers within 5 minutes, and a single film of the aqueous dispersion (vinylidene chloride copolymer layer) is collected. The single film collected is folded four times to prepare a measurement sample. (Method of measuring YI) The measurement method involves placing a measurement sample 30 mm from a light source (e.g., AS ONE's "LUV-16") and irradiating it with ultraviolet light from the light source for 5 hours in a room at 20°C. After irradiation, the yellowness YI is measured with a color difference meter using the transmittance measurement method described below. The smaller the difference (ΔYI=YI-YI0) between the YI of the film (or paper laminate) after ultraviolet irradiation and the YI of the film (or paper laminate) before ultraviolet irradiation (YI0), the higher the ultraviolet resistance. ΔYI is preferably 7.0 or less, more preferably 6.0 or less, even more preferably 5.0 or less, still more preferably 4.0 or less, and particularly preferably 3.0 or less. (Transmission measurement method) The transmittance of the measurement sample is measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc. The YI value is the average of three measurements. The measurement conditions are as follows. Color system: L*a*b* Index: YI ASTM E313-96 Field of view: 10° Main light source: D65 Secondary light source: None

[0112] (4) Dissolution The elution rate of the UV absorber is a parameter for evaluating the risk of migration of the UV absorber into the contents when a film or paper laminate coated with the aqueous dispersion is used as a packaging material. Since migration of the UV absorber into the contents may cause health damage, it is preferable that the elution rate is small. The elution rate varies depending on the type of solvent used in the test. When the UV absorbent is a hydrophilic or water-containing substance, water is used as a solvent to evaluate the elution, and when the UV absorbent is a hydrophobic substance, toluene is preferably used as a solvent to evaluate the elution. The measurement method is to take 0.2 g of dried vinylidene chloride copolymer and immerse it in 10 mL of solvent. After leaving it for 12 hours to remove the dried material, the absorbance of the solvent used for immersion at a wavelength of 360 nm is measured using the above-mentioned UV-Visible Spectroscopy <When the sample is liquid>. The obtained absorbance is used as an index of dissolution. Higher absorbance means higher dissolution, which is not preferable. If the absorbance exceeds 2.0, dilute the sample so that the absorbance is between 0.1 and 1.0 and measure it. Then, since the above-mentioned Beer-Lambert equation suggests that absorbance is proportional to concentration, the absorbance is multiplied by the dilution factor to convert it. For example, if the absorbance obtained by 10-fold dilution is 0.5, the original absorbance can be converted to 5.0. The dried vinylidene chloride copolymer may be obtained by drying an aqueous dispersion of the vinylidene chloride copolymer, or by separating it from a film or paper laminate by the above-mentioned <Method for separating vinylidene chloride copolymer (layer) from a film>.

[0113] The absorbance when water is used as a solvent is preferably less than 0.02, more preferably less than 0.015, even more preferably less than 0.01, and particularly preferably less than 0.005. If it is less than 0.005, it can be determined that almost all of the ultraviolet absorbent is not eluted. The absorbance when toluene is used as a solvent is preferably less than 10, more preferably less than 1.4, even more preferably less than 1.0, still more preferably less than 0.5, even more preferably less than 0.2, and particularly preferably less than 0.1. If the absorbance is less than 0.1, it can be determined that almost all of the ultraviolet absorbent is not eluted.

[0114] (5) Measurement method for oxygen permeability Oxygen transmission rate [cc / (m 2 ·day)] can be measured for a film (or paper laminate) having a vinylidene chloride copolymer layer coated with an aqueous dispersion, under conditions of 23°C and 0% RH, using a water vapor transmission rate measuring device (for example, "OXTRAN 2 / 22" manufactured by MOCON). The average value measured between 48 hours and 60 hours after the start of the measurement is regarded as the oxygen permeability, and the average value obtained by performing the measurement four times is regarded as the oxygen permeability of the film (or paper laminate). The lower the oxygen permeability, the better the protection of the contents from oxidation when a film (or paper laminate) having a vinylidene chloride copolymer layer is used as a packaging material. 2 per 19cc / (m 2 ·day) or less, and more preferably 11 cc / (m 2 ·day) or less, and more preferably 9.0 cc / (m 2 ·day) or less, and particularly preferably 5 cc / (m 2 ·day). The oxygen permeability can be reduced by increasing the dry coating amount, but multiple coatings are disadvantageous in terms of processing costs. 2 9.0cc / (m 2 If it is less than 10-20g / m 2 On the other hand, for applications requiring gas barrier properties, such as pharmaceutical packaging, a coating weight of 40 g / m is recommended from the viewpoint of gas barrier properties. 2 ~200g / m 2A high coating weight of 10g / m2 is used. 2 19cc / (m 2 If the storage temperature is within 100°C (days), the contents can be sufficiently protected from oxygen even in such high barrier applications.

[0115] (6) Measurement method of average particle size The average particle size of the particles (particles of the vinylidene chloride copolymer, the ultraviolet absorber, and the polymer compound other than the vinylidene chloride copolymer, etc.) contained in the aqueous dispersion can be measured by the following method. The aqueous dispersion is diluted with water so that the solid content becomes 0.1% by mass, and is measured using a particle size distribution measuring device ("FPAR-1000" manufactured by Otsuka Electronics Co., Ltd.) The average particle size obtained from the cumulant analysis is regarded as the average particle size of the particles contained in the aqueous dispersion.

[0116] (7) Haze measurement method The film having the vinylidene chloride copolymer layer is measured with a haze meter (for example, "NDH 7000II" manufactured by Nippon Denshoku Industries Co., Ltd.) to determine the haze [%]. The lower the haze, the more excellent the transparency of the film. Dry coating amount of the aqueous dispersion: 10 g / m 2 The haze is preferably 3.5% or less, more preferably 3.0% or less, even more preferably 2.7% or less, and particularly preferably 2.0% or less, per dry coating amount. If it exceeds 3.5%, the coating gives an impression of opacity when observed with the naked eye. The haze increases with increasing coating amount. 2 If the density is less than 3.5% per unit area, the most common density range is 10-20g / m for food packaging applications. 2 On the other hand, for applications that require gas barrier properties, such as pharmaceutical packaging, a coating weight of 40 g / m is recommended from the perspective of gas barrier properties. 2 ~200g / m 2 A high coating weight of 10 g / m2 is used. 2 If the content ratio is 2.0% or less per unit area, visibility of the contents can be sufficiently ensured in such high barrier applications.

[0117] (8) UV absorption The ultraviolet absorbing properties of a film or paper laminate having a vinylidene chloride copolymer layer can be evaluated by measuring the absorbance of the film or paper laminate by ultraviolet-visible spectroscopy. The higher the absorbance, the better the ultraviolet absorbing properties, and the more the contents can be protected when used as a packaging material. Dry coating amount 10 g / m 2 The absorbance per m is preferably 0.08 or more, more preferably 0.15 or more, even more preferably 0.20 or more, and particularly preferably 0.30 or more. The UV absorbency increases with increasing coating amount. 2 If the absorbance per unit area is 0.20 or more, it is suitable for the 10 to 20 g / m2 range, which is the most common for food packaging applications. 2 On the other hand, in applications where gas barrier properties are particularly required, such as pharmaceutical packaging, a coating weight of 40 g / m2 is required from the viewpoint of gas barrier properties. 2 ~200g / m 2 A high coating weight of 10 g / m2 is used. 2 An absorbance of 0.08 or more per 1000 nm can provide sufficient protection for the contents from ultraviolet light in such high barrier applications.

[0118] [Film of the second embodiment] The film as a second aspect of the present embodiment is a multilayer film having a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of a vinylidene chloride copolymer, and is characterized in that the vinylidene chloride copolymer layer has an absorption coefficient ε5 of 0.01 L / (g cm) or more at a wavelength of 360 nm. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above.

[0119] The film of the present embodiment preferably has a vinylidene chloride copolymer layer on a film substrate. The film substrate is not particularly limited, but representative examples include films made of polyvinyl chloride, polyester, polyamide, polypropylene, polyethylene, cyclic polyolefin, and cellophane. In the case of blister packaging, a film made of polyvinyl chloride is used. The thickness of the film substrate may vary depending on the material used, but may usually be 8 to 300 μm.

[0120] In addition, the film of the present embodiment may optionally include a layer of a functionally adjusted copolymer mainly composed of a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer. For example, such a layer may be a primer layer formed on a film substrate using an aqueous resin emulsion or an acrylic dispersion, and the vinylidene chloride copolymer layer may be provided thereon.

[0121] The film of the present embodiment may optionally further include at least one vinylidene chloride copolymer layer having chemical or physical properties different from those of the vinylidene chloride copolymer of the vinylidene chloride copolymer layer of the present embodiment. For example, a film having a vinylidene chloride copolymer layer having a different composition on the vinylidene chloride copolymer layer of the present embodiment for the purpose of preventing blocking or improving the slip property of the film may be included. Another example is a film in which the vinylidene chloride copolymer layer of the present embodiment and a vinylidene chloride copolymer layer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A film having this structure is expected to have high impact resistance. In the case of a film having a plurality of kinds of vinylidene chloride copolymer layers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers.

[0122] The outermost surface of the film of the present embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the film is used as a packaging material.

[0123] The vinylidene chloride copolymer layer of the film of this embodiment has ultraviolet absorption properties due to the inclusion of an ultraviolet absorber (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer). Examples of the ultraviolet absorbent (including an ultraviolet absorbing monomer) contained in the vinylidene chloride copolymer layer include the same ones as those contained in the water dispersion of the above-mentioned first embodiment, and the content may be the same.

[0124] It is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorbent. Such a film has excellent recyclability because the film base can be recovered without the ultraviolet absorbent by separating the vinylidene chloride copolymer layer containing the ultraviolet absorbent. In addition, when used as a packaging material, the layer not containing the ultraviolet absorbent is made to be the layer in contact with the contents, thereby preventing the ultraviolet absorbent from migrating to the contents. Any method can be used to determine whether each layer contains an ultraviolet absorber, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether or not a vinylidene chloride copolymer layer is a layer having ultraviolet absorbing properties according to this embodiment. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method of separating and dissolving each layer to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether or not the layer contains an emulsifier, and if it contains an emulsifier, it can be said to be a vinylidene chloride copolymer layer having ultraviolet absorbing properties according to this embodiment.

[0125] In addition, whether or not each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the procedure described above in <Determination of the presence of a hydrophilic ultraviolet absorber>. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when the film is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.

[0126] The coating weight of the vinylidene chloride copolymer layer is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 By increasing the coating mass, the gas barrier properties of the film as a whole can be improved. In order to increase the coating weight, a method of repeatedly applying the aqueous dispersion multiple times is generally used.

[0127] The film of the present embodiment is preferably used as a blister package, and the resulting blister package exhibits excellent water vapor barrier properties and ultraviolet light absorption properties. Furthermore, in addition to being applied to blister packages, the film of this embodiment can also be used as it is as a coating agent to form a clear film.

[0128] The method for applying the aqueous dispersion of the vinylidene chloride copolymer to the surface of the substrate can be a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc. After the aqueous dispersion is applied to the film substrate, the film is usually dried by keeping it at room temperature or under heating for a predetermined time.

[0129] The absorption coefficient ε5 of the vinylidene chloride copolymer layer at a wavelength of 360 nm is preferably 0.03 L / (g·cm) or more, more preferably 0.08 L / (g·cm) or more, even more preferably 0.14 L / (g·cm) or more, and even more preferably 0.29 L / (g·cm) or more. The larger the absorption coefficient ε5 of the vinylidene chloride copolymer layer, the more the deterioration of the contents, the substrate, and the vinylidene chloride copolymer itself due to ultraviolet rays can be suppressed when the film is used as a packaging material. The absorption coefficient ε5 of the vinylidene chloride copolymer layer is preferably 1.00 L / (g·cm) or less, more preferably 0.76 L / (g·cm) or less, and even more preferably 0.61 L / (g·cm) or less. The absorbance A5 of the vinylidene chloride copolymer layer at a wavelength of 360 nm can be measured by using the above-mentioned ultraviolet-visible spectroscopy. Examples of methods for controlling the extinction coefficient ε5 include, as in the case of the aqueous dispersion of the first embodiment described above, a method for increasing the absorbance at a wavelength of 360 nm by adding an ultraviolet absorber to the aqueous dispersion forming the vinylidene chloride copolymer layer or synthesizing a vinylidene chloride copolymer using an ultraviolet absorbing monomer.

[0130] The absorption coefficient ε5 of the vinylidene chloride copolymer can also be estimated from the converted absorption coefficient of the film of this embodiment, similarly to the case of a film having a vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the first embodiment described above.

[0131] [Paper laminate according to the third embodiment] The paper laminate which is a third aspect of this embodiment is a multi-layer paper having a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of a vinylidene chloride copolymer, and is characterized in that the extinction coefficient ε6 of the vinylidene chloride copolymer layer at a wavelength of 360 nm is 0.01 L / (g cm) or more. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above. The paper laminate of this embodiment can be used as moisture-proof paper.

[0132] The paper laminate of this embodiment preferably has a vinylidene chloride copolymer layer on a paper substrate. The paper substrate may be the same as the paper laminate having a vinylidene chloride copolymer layer coated with the aqueous dispersion of the first embodiment described above. The paper substrate may be a single layer, or may be made up of two or more layers.

[0133] The paper laminate of this embodiment may optionally further comprise at least one layer of a vinylidene chloride copolymer having chemical or physical properties different from those of the vinylidene chloride copolymer contained in the vinylidene chloride copolymer layer of this embodiment. For example, there is a paper laminate in which an aqueous dispersion of a vinylidene chloride copolymer having a different composition is applied onto the vinylidene chloride copolymer layer of this embodiment for the purpose of preventing blocking or improving the slipperiness of the paper laminate. Another example is a paper laminate in which the vinylidene chloride copolymer layer of the present embodiment and a layer of a vinylidene chloride copolymer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A paper laminate having this structure is expected to have high impact resistance. In the case of such a paper laminate having a plurality of types of vinylidene chloride copolymer layers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers.

[0134] The outermost surface of the paper laminate of this embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer. With such a layer configuration, when an oxidizing agent is contained in the vinylidene chloride copolymer layer, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the paper laminate is used as a packaging material.

[0135] The coating weight of the vinylidene chloride copolymer layer is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 By increasing the coating mass, the water vapor barrier properties of the entire paper laminate can be improved. However, the thicker the vinylidene chloride copolymer layer, the smaller the discoloration degree of the vinylidene chloride copolymer layer per unit volume when viewed as a single sheet of paper laminate, but the larger the discoloration degree appears when rolled up. Thus, the thicker the vinylidene chloride copolymer layer of the paper laminate, the greater the effect of the vinylidene chloride copolymer of this embodiment in suppressing yellowing in the rolled state.

[0136] Furthermore, the paper laminate of this embodiment may optionally include, in addition to the vinylidene chloride copolymer layer, a layer of a functionally adjusted copolymer mainly composed of a monomer other than vinylidene chloride that has high polymerization activity. For example, such a layer may be a primer layer formed on a paper substrate using an aqueous resin emulsion or an acrylic dispersion, and a vinylidene chloride copolymer layer may be provided thereon.

[0137] The vinylidene chloride copolymer layer of the paper laminate of this embodiment has ultraviolet absorption properties due to the inclusion of an ultraviolet absorbent (including cases where the vinylidene chloride copolymer contains structural units derived from ultraviolet absorbing monomers). Examples of the ultraviolet absorbent (including an ultraviolet absorbing monomer) contained in the vinylidene chloride copolymer layer include the same ones as those contained in the water dispersion of the above-mentioned first embodiment, and the content may be the same.

[0138] It is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorbent. Such a paper laminate can be recovered without the ultraviolet absorbent by separating the vinylidene chloride copolymer layer containing the ultraviolet absorbent, and has excellent recyclability. In addition, when used as a packaging material, the layer not containing the ultraviolet absorbent is made the layer in contact with the contents, thereby preventing the ultraviolet absorbent from migrating to the contents. Any method can be used to determine whether each layer contains an ultraviolet absorber, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether or not a vinylidene chloride copolymer layer is a layer having ultraviolet absorbing properties according to this embodiment. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method of separating and dissolving each layer to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether or not the layer contains an emulsifier, and if it contains an emulsifier, it can be said to be a vinylidene chloride copolymer layer having ultraviolet absorbing properties according to this embodiment.

[0139] In addition, whether or not each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the procedure described above in <Determination of the presence of a hydrophilic ultraviolet absorber>. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when the film is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.

[0140] When the paper base material is a transparent paper such as glassine paper, it becomes a paper material with gas barrier properties and ultraviolet absorbing properties. In recent years, paper packaging has been attracting attention due to the increasing need to reduce the amount of plastic. Since paper does not usually have gas barrier properties, a polyvinylidene chloride copolymer layer, an ethylene-vinyl alcohol copolymer layer, a polyvinyl alcohol layer, etc. are applied to the paper base material to impart gas barrier properties. The ethylene-vinyl alcohol copolymer layer and the polyvinyl alcohol layer have high oxygen barrier properties but low water vapor barrier properties. On the other hand, the polyvinylidene chloride copolymer layer has high oxygen barrier properties and water vapor barrier properties, and is excellent in that it can block oxygen and water vapor alone. In addition, since the monomer is synthesized using salt as a raw material, it is also excellent in that it uses much less petroleum than other materials. Although paper has a drawback in that it discolors and deteriorates due to ultraviolet light, the paper laminate having the vinylidene chloride copolymer layer of the present embodiment suppresses ultraviolet deterioration of the paper because the vinylidene chloride copolymer layer has ultraviolet light absorbing properties, and furthermore, when used as a packaging material, ultraviolet deterioration of the contents can also be prevented. In the case of a resin-based film, it is possible to prevent deterioration to some extent by introducing an ultraviolet absorber into the film, but in the case of paper, it is difficult or disadvantageous in terms of cost to introduce an ultraviolet absorber into the paper. Therefore, in general, when imparting ultraviolet absorption, it is necessary to provide an ultraviolet absorbing layer separately from a gas barrier layer, but the vinylidene chloride copolymer layer of the present embodiment has oxygen barrier properties, water vapor barrier properties, and ultraviolet absorption properties by itself, and therefore can block oxygen, water vapor, and ultraviolet rays all at once.

[0141] As a method for applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment to the paper substrate, a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc., can be used for the surface of the substrate. After application to the paper substrate, the coating is usually dried by keeping it at room temperature or under heating for a predetermined time.

[0142] The absorption coefficient ε6 of the vinylidene chloride copolymer layer at a wavelength of 360 nm is preferably 0.03 L / (g·cm) or more, more preferably 0.08 L / (g·cm) or more, even more preferably 0.14 L / (g·cm) or more, and even more preferably 0.29 L / (g·cm) or more. The larger the absorption coefficient ε6 of the vinylidene chloride copolymer layer, the more the deterioration of the contents, the substrate, and the vinylidene chloride copolymer itself due to ultraviolet rays can be suppressed when the film is used as a packaging material. The absorption coefficient ε6 of the vinylidene chloride copolymer layer is preferably 1.00 L / (g·cm) or less, more preferably 0.76 L / (g·cm) or less, and even more preferably 0.61 L / (g·cm) or less. The absorbance A6 of the vinylidene chloride copolymer layer at a wavelength of 360 nm can be measured by using the above-mentioned ultraviolet-visible spectroscopy. Examples of methods for controlling the extinction coefficient ε6 include, as in the case of the aqueous dispersion of the first embodiment described above, a method for increasing the absorbance at a wavelength of 360 nm by adding an ultraviolet absorber to the aqueous dispersion forming the vinylidene chloride copolymer layer or synthesizing a vinylidene chloride copolymer using an ultraviolet absorbing monomer. EXAMPLES

[0143] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, when "parts" or "%" is used, it means "parts by mass" or "% by mass", respectively, unless otherwise specified.

[0144] <Polymerization Example of Water Dispersion> [Comparative Example 1] An aqueous dispersion of a vinylidene chloride copolymer was prepared in the same manner as in Example 1 of Patent Document 1. In a pressure-resistant reactor with glass lining, 100 parts by mass of ion-exchanged water, 0.2 parts by mass of sodium dodecyl sulfonate, and 0.2 parts by mass of sodium persulfate were charged, and after degassing, the temperature of the contents was kept at 50°C. In a separate container, 90 parts by mass of vinylidene chloride (VDC), 9.7 parts by mass of methyl acrylate (MA), and 0.3 parts by mass of acrylic acid (AA) were weighed and mixed to prepare a raw material monomer mixture. After adding 10 parts by mass of the raw material monomer mixture to the reactor and reacting for about 10 hours, the remaining 90 parts by mass of the raw material monomer mixture and 0.7 parts by mass of sodium dodecyl sulfonate were added in total while adjusting the time to 25 hours so that the internal temperature does not rise, and then the reaction was allowed to proceed until the internal pressure decreased to 0.1 MPa. After that, the mixture was heated to 60°C and the residual monomers were removed under reduced pressure to obtain an aqueous dispersion.

[0145] [Comparative Example 2] An aqueous dispersion of a vinylidene chloride copolymer was prepared in the same manner as in Example 1 of Patent Document 4. In a glass-lined pressure reactor, 57 parts of pure water, 0.03 parts of sodium D-araboascorbate, and 0.2 parts of sodium alkylsulfonate were charged relative to a total mass of 100 parts of monomers, and the mixture was degassed while stirring, and the temperature of the contents was maintained at 45°C. A raw monomer mixture with a mass composition ratio of VDC / MMA / AN=90.1 / 9.4 / 0.5 was prepared in a separate container. 20 parts of the raw monomer mixture were added to the pressure reactor in one go, and polymerization was carried out until the internal pressure dropped. Then, the remaining raw monomer mixture (80 parts) was continuously measured and pressurized. In parallel, an initiator prepared by dissolving 0.014 parts of t-butyl hydroperoxide in 3.5 parts of pure water, a reducing agent prepared by dissolving 0.015 parts of sodium D-araboascorbate in 3.5 parts of pure water, and an emulsifier prepared by dissolving 1.6 parts of sodium alkyldiphenyletherdisulfonate in 2.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were kept at 45°C while being stirred, and the reaction was allowed to proceed until the internal pressure had dropped sufficiently. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. After removing unreacted monomers from the aqueous dispersion thus obtained by steam stripping, the solid content was adjusted to 50-60%.

[0146] [Comparative Example 3] An aqueous dispersion was synthesized in the same manner as in Comparative Example 2, except that the composition of the raw material monomers was VDC / MAN=90 / 10.

[0147] [Example 1] An aqueous dispersion of a vinylidene chloride copolymer was prepared in the same manner as in Example 1 of Patent Document 4. In a glass-lined pressure reactor, 57 parts of pure water, 0.03 parts of sodium D-araboascorbate, and 0.2 parts of sodium alkylsulfonate were charged per 100 parts of total monomer mass, and the mixture was degassed while stirring, and the temperature of the contents was maintained at 45°C. In a separate container, a raw monomer mixture with a mass composition ratio of VDC / MAN / RUVA-93=90 / 9.5 / 0.5 was prepared. 20 parts of the raw monomer mixture were added to the pressure reactor in one go, and polymerization was carried out until the internal pressure dropped. Then, the remaining raw monomer mixture (80 parts) was continuously measured and pressurized. In parallel, an initiator prepared by dissolving 0.014 parts of t-butyl hydroperoxide in 3.5 parts of pure water, a reducing agent prepared by dissolving 0.015 parts of sodium D-araboascorbate in 3.5 parts of pure water, and an emulsifier prepared by dissolving 1.6 parts of sodium alkyldiphenyletherdisulfonate in 2.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were kept at 45°C while being stirred, and the reaction was allowed to proceed until the internal pressure had dropped sufficiently. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. After removing unreacted monomers from the aqueous dispersion thus obtained by steam stripping, the solid content was adjusted to 60%. Here, RUVA-93 is a polymerizable benzotriazole-based ultraviolet absorber (ultraviolet absorbing monomer) (CAS No. 96478-09-0) sold by Otsuka Chemical Co., Ltd. Since it is a powdered compound, it was thoroughly stirred after mixing the raw monomers and thoroughly dissolved in the other monomers before use. When the absorbance of the water-soluble component at a wavelength of 360 nm was measured according to the procedure described below (Determining the presence of a hydrophilic ultraviolet absorber), the absorbance was less than 0.01. Since no hydrophilic ultraviolet absorber was added, it was confirmed that the product did not contain a hydrophilic ultraviolet absorber. (Determining the presence of hydrophilic UV absorbers) 1 g of the dried aqueous dispersion of vinylidene chloride copolymer was dissolved in 20 mL of tetrahydrofuran. 30 mL of pure water was slowly added dropwise to the resulting 20 mL of solution over 1 hour. The mixture was stirred with a stirrer during the addition. After stopping the stirring and leaving the mixture to stand for 24 hours, 5 mL of the supernatant was taken and filtered through a membrane filter. The resulting filtrate was measured using a visible / ultraviolet spectrophotometer (Shimadzu Corporation's "UV-1280") to determine the absorbance of the water-soluble components at a wavelength of 360 nm.

[0148] [Example 2] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MA / RUVA-93=90 / 9 / 1.

[0149] [Example 3] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MA / RUVA-93=90 / 8 / 2.

[0150] [Example 4] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN / RUVA-93=90 / 9 / 1.

[0151] [Example 5] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN / MMA / RUVA-93=91 / 5 / 2 / 2.

[0152] [Example 6] The aqueous dispersion of this example was prepared by adding a polymeric ultraviolet-absorbing aqueous dispersion (a water dispersion of a polymeric ultraviolet absorber) to the aqueous dispersion synthesized in Comparative Example 3 so that the dry mass was 15 parts by mass when the total mass of the vinylidene chloride copolymer was 100 parts by mass. The polymeric ultraviolet absorbing water dispersion used here was obtained by emulsion polymerization of a raw material monomer mixture adjusted to a mass composition ratio of MMA / RUVA-93 = 90 / 10. The solid content of the polymeric ultraviolet absorbing water dispersion was 30%, and the average particle size of the polymeric ultraviolet absorber particles was 131 nm.

[0153] [Example 7] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN / MMA=91 / 5 / 4. The polymeric ultraviolet-absorbing water dispersion obtained in the same manner as in Example 6 was added to the synthesized water dispersion in an amount of 10 parts by mass on a dry basis when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing the water dispersion of this example.

[0154] [Example 8] An aqueous dispersion was prepared in the same manner as in Example 6, except that the amount of the polymeric ultraviolet absorbing aqueous dispersion added was 5 parts by mass.

[0155] [Example 9] An aqueous dispersion was prepared in the same manner as in Example 7, except that the amount of the polymeric ultraviolet absorbing aqueous dispersion added was 3 parts by mass.

[0156] [Example 10] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN=91 / 9. The polymeric ultraviolet-absorbing water dispersion obtained in the same manner as in Example 6 was added to the synthesized water dispersion in an amount of 1 part by mass on a dry basis when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing the water dispersion of this example.

[0157] [Comparative Example 4] An aqueous dispersion was prepared in the same manner as in Example 6, except that the amount of the polymeric ultraviolet absorbing aqueous dispersion added was 25 parts by mass.

[0158] [Example 11] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN=91 / 9. A polymeric ultraviolet absorbing water dispersion (a water dispersion of a polymeric ultraviolet absorber) was added to the synthesized water dispersion so that the dry mass was 5 parts by mass when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing the water dispersion of this example. The polymeric ultraviolet absorbing water dispersion used here was obtained by emulsion polymerization of a raw material monomer mixture adjusted to a mass composition ratio of MMA / RUVA-93 = 90 / 10. The solid content of the polymeric ultraviolet absorbing water dispersion was 30%, and the average particle size of the polymeric ultraviolet absorber particles was 22 nm.

[0159] [Example 12] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN / MMA=91 / 5 / 4. A hydrophilic ultraviolet absorber was added to the synthesized aqueous dispersion so that the dry mass was 1 part by mass when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing an aqueous dispersion of this example. As the hydrophilic ultraviolet absorbent, Seesorb 101S (Shipro Chemical Co., Ltd., CAS No. 71776-12-0) was used, which was dissolved in water to a concentration of 10 mass % and then added to the water dispersion. The absorbance of the water-soluble component at a wavelength of 360 nm was measured according to the procedure described above (Determination of the presence of a hydrophilic UV absorber) and was found to be 0.4.

[0160] [Example 13] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN=91 / 9. An aqueous dispersion of a non-polymerizable ultraviolet absorber was added to the synthesized aqueous dispersion so that the dry mass was 5 parts by mass when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing the aqueous dispersion of this example. As the aqueous dispersion of the non-polymerizable ultraviolet absorber, a aqueous dispersion of a triazine-based ultraviolet absorber, Chiguard 5400WB (Kusumoto Chemicals Co., Ltd., CAS No. 153519-44-9), was used. The average particle size of the non-polymerizable ultraviolet absorber particles was 216 nm. When the latex after the addition of the aqueous dispersion of the non-polymerizable UV absorber was filtered, a small amount of residue was obtained. This is considered to be due to the fact that a part of the non-polymerizable UV absorber was not dispersed well during mixing and precipitated.

[0161] [Example 14] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw material monomers was VDC / MAN / MMA=91 / 5 / 4. An aqueous dispersion of the same non-polymerizable ultraviolet absorber as in Example 13 was added to the synthesized aqueous dispersion so that the dry mass was 10 parts by mass when the total mass of the vinylidene chloride copolymer was 100 parts by mass, thereby producing an aqueous dispersion of this example. When the latex after the addition of the aqueous dispersion of the non-polymerizable UV absorber was filtered, a small amount of residue was obtained. This is considered to be due to the fact that a part of the non-polymerizable UV absorber was not dispersed well during mixing and precipitated.

[0162] [Example 15] An aqueous dispersion was synthesized in the same manner as in Example 1, except that 2-hydroxy-4-methacryloxybenzophenone was used instead of RUBA-93 as the polymerizable ultraviolet absorber (ultraviolet absorbing monomer) and the composition of the raw material monomers was VDC / MAN / 2-hydroxy-4-methacryloxybenzophenone=91 / 8 / 1.

[0163] [Example 16] An aqueous dispersion was synthesized in the same manner as in Example 1, except that the composition of the raw monomers was VDC / MAN=91 / 9, and 1 part by mass of a non-polymerizable ultraviolet absorber Adeka STAB LA-36 (ADEKA CORPORATION) was dissolved in 100 parts by mass of the raw monomer mixture to perform polymerization.

[0164] [Comparative Example 5] An aqueous dispersion of Comparative Example 1 was prepared by adding 1 part by mass of an ultraviolet absorber Sumisorb 300 (Sumitomo Chemical) to the aqueous dispersion of Comparative Example 1. Sumisorb 300 is 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chlorobenzotriazole, which is a water-insoluble powder, i.e., a hydrophobic ultraviolet absorber. When the aqueous dispersion was filtered through a wire mesh after adding Sumisorb 300, a powder was obtained. This is considered to be the result of the UV absorber being insoluble in water and thus precipitating.

[0165] [Example 17] The composition of the raw material monomers was VDC / MAN / RUVA-93=92 / 7 / 1, and 3.1 parts by mass of homomethyl methacrylate seed latex (average particle size 50 nm) per 100 parts by mass of the raw material monomer mixture was added to the polymerization machine before polymerization in the same manner as in Example 1. The amount of pure water was adjusted to a total of 57 parts by mass, taking into account the amount of water brought in by the seeds. It was visually confirmed that the residue remaining in the polymerization machine after polymerization was smaller than the residue after polymerization in Examples 4 and 5. In addition, 40 mL of the obtained aqueous dispersion was transferred to a 50 mL polypropylene bottle and stored in an oven at 60° C., whereupon the aqueous dispersions of Examples 4 and 5 solidified in about 17 days, whereas the aqueous dispersion of Example 17 did not solidify for 30 days or longer. This result indicates that the aqueous dispersion of Example 17 has excellent aggregation stability.

[0166] The following measurements were carried out using the obtained aqueous dispersion of vinylidene chloride copolymer. The coated films used for the measurements were prepared by the following procedures. (Preparation of coated film) A polyethylene terephthalate (PET) film (thickness 12 μm) that had been subjected to corona discharge treatment was used as the substrate. The aqueous dispersion of the vinylidene chloride copolymer obtained in each of the Examples and Comparative Examples was applied onto the substrate using a Mayer rod until the coating mass after drying was 10 g / m 2 The coating was applied so that the coating solution was applied to the film, and the coating solution was dried in a hot air circulating dryer at 85° C. for 15 seconds. The resulting coated film was stored in a 40° C. oven for 24 hours and then subjected to each measurement.

[0167] (Monomer composition) The monomer composition of the vinylidene chloride copolymer was evaluated by dissolving a sample taken by the following method in tetrahydrofuran-d8 and performing NMR measurement. 10 mL of the aqueous dispersion was freeze-dried, and 0.5 g of the freeze-dried product was collected. The freeze-dried product was dissolved in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or more, and 40 mL of acetone was added dropwise to the solution. The resulting precipitate was filtered, and the remaining insoluble matter was collected. The collected insoluble matter was used as the measurement sample. The NMR measurement conditions were as follows. Equipment: JEOL RESONANCE ECS400 (1H), Bruker Biospin Avance600 (13C) Observed nuclei: 1H (399.78MHz), 13C (150.91MHz) Pulse program: Single pulse (1H), zgig30 (13C) Accumulation count: 256 times (1H), 10,000 times (13C) Lock solvent: THF-d8 Chemical shift reference: THF (1H: 180 ppm, 13C: 67.38 ppm) The monomers were assigned using the NMR spectrum obtained, and the composition of the vinylidene chloride copolymer was identified by integrating the peaks. The type of monomers contained was clear from the monomers used. As an example, for a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate, and acrylic acid, 13 In the C-NMR spectrum, the content of structural units derived from vinylidene chloride was determined by integrating from 80 to 90 ppm, the content of structural units derived from methacrylonitrile was determined by integrating from 110 to 130 ppm, the content of structural units derived from methyl methacrylate was determined by integrating from 170 to 180 ppm, and the content of structural units derived from acrylic acid was determined by integrating from 180 to 200 ppm, and the composition ratio of each monomer in the total was calculated. In the case of a copolymer containing structural units derived from methyl acrylate instead of methyl methacrylate, the calculation is performed by substituting methyl acrylate for methyl methacrylate in the above calculation method. In the case of a copolymer containing structural units derived from acrylonitrile instead of methacrylonitrile, the calculation is performed by substituting acrylonitrile for methacrylonitrile in the above calculation method. As a result of the above measurements, it was found that the vinylidene chloride copolymers obtained in the Examples and Comparative Examples had the same monomer composition as the charged composition.

[0168] (Solids content measurement) 2.5 g of the aqueous dispersion was weighed into a solid content meter SMART SYSTEM5 manufactured by CEM, and measurements were performed under an environment of 20°C and 50% RH. The results of three measurements were averaged, and the solid content (%) was calculated using the formula (dry mass / mass of aqueous dispersion) x 100.

[0169] (Calculation of extinction coefficient ε1) The aqueous dispersion was applied to aluminum foil at a coating weight of 10 g / m2 after drying. 2The dried material was obtained by applying the coating solution so that the coating would become 0.2% by mass and drying it in a hot air dryer at 100°C for 1 minute. If the coating was liquid or moisture was still present, it was placed in an oven for a few more minutes and dried until it was no longer liquid. The dried material obtained was added to tetrahydrofuran so that the concentration was 0.2% by mass and dissolved by stirring at room temperature. If any residue remained, it was heated and stirred within the range where the tetrahydrofuran did not boil, and if it still did not dissolve, the liquid was filtered to remove the insoluble matter. The absorbance A1 of the obtained solution at a wavelength of 360 nm was measured by ultraviolet-visible spectroscopy using a UV-visible spectrophotometer UV1280 manufactured by Shimadzu Corporation. Reference:Tetrahydrofuran Cell: Quartz cell (optical path length 1 cm) The concentration of the dried material dissolved in tetrahydrofuran was defined as x (g / L) and the optical path length as l (cm), and the extinction coefficient ε1 (L / (g cm)) was calculated using the Beer-Lambert equation below. Beer-Lambert formula: A1=ε1×x×l

[0170] (Calculation of the converted absorption coefficient of the coated film) The obtained coated film and the PET film used to prepare the coated film were measured by ultraviolet-visible spectroscopy using a color difference meter CM-5 manufactured by Konica Minolta, Inc., to determine the dry coating amount of 10 g / m2. 2 The absorbance at a wavelength of 360 nm per 360all , absorbance A 360PET The measurement conditions were as follows: Field of view: 10° Main light source: D65 Secondary light source: None Next, the absorbance A of the PVDC layer at a wavelength of 360 nm 360PVDC was calculated by the following formula. A 360PVDC =A 360all -A 360PET Obtained A 360PVDC By substituting the thickness d (cm) of the PVDC layer into the Beer-Lambert equation below, the extinction coefficient ε4 (cm-1 The thickness d of the PVDC layer was calculated by subtracting the thickness of the PET film from the total thickness of the coated film. Beer-Lambert formula: A 360PVDC = ε4×d Next, the converted ε4 was calculated using the following conversion formula. Note that the density of the PVDC layer (g / cm 3 ) was measured using a dry density meter (Shimadzu Corporation, "AccuPyc 2 1340") using helium gas. Conversion ε4 = ε4 / (1000 × density of PVDC layer)

[0171] (Oxygen permeability measurement) The obtained coated film was measured at 23°C and 0% RH using a water vapor transmission rate measuring device (MOCON "OXTRAN 2 / 22") to determine the dry coating amount of 10 g / m 2 Oxygen permeability per unit [cc / (m 2 The average value of the measurements taken between 48 hours and 60 hours after the start of the measurements was regarded as the oxygen permeability, and the average value of four measurements was regarded as the oxygen permeability of the coated film.

[0172] (UV absorbance measurement) The obtained coated film was measured by ultraviolet-visible spectroscopy using a color difference meter CM-5 manufactured by Konica Minolta, Inc. to determine the dry coating amount of 10 g / m 2 The absorbance at a wavelength of 360 nm was measured under the following measurement conditions: Field of view: 10° Main light source: D65 Secondary light source: None

[0173] (Determining whether a single film has gas barrier properties and UV absorption properties) The obtained coated films were judged according to the following criteria as to whether or not the vinylidene chloride copolymer layer alone (single film) had gas barrier properties and ultraviolet absorbing properties. Yes: Absorption coefficient ε1 is 0.01 L / (g cm) or more, and the dry coating amount is 10 g / m 2 The oxygen permeability is 19cc / (m 2·day) or less None: Absorption coefficient ε1 is less than 0.01 L / (g cm) or dry coating amount is 10 g / m 2 The oxygen permeability is 19cc / (m 2 ·day) is super

[0174] (Haze measurement) The haze [%] of the obtained coated film was measured using a haze meter ("NDH 7000II" manufactured by Nippon Denshoku Industries Co., Ltd.) The lower the haze, the more transparent the coated film is evaluated to be (the better the visibility of the contents when used as a packaging material).

[0175] (Measurement of water elution of UV absorbers) The water elution of the resulting coated film was determined by the following method. From the obtained coating film, 0.2 g of a dried vinylidene chloride copolymer was collected by peeling and / or scraping with tweezers. The collected dried product was immersed in 10 mL of water and left for 12 hours. The dried product was removed from the water, and the absorbance of the water at a wavelength of 360 nm was measured using a UV-Visible Spectrophotometer UV1280 manufactured by Shimadzu Corporation. Reference: Sample solvent (THF if the sample was dissolved in THF) Cell: Quartz cell (optical path length 1 cm) When the absorbance exceeded 2.0, the solution was diluted so that the absorbance was between 0.1 and 1.0. The absorbance was calculated by multiplying the measured value by the dilution ratio. The absorbance was used as an index of dissolution, and it was evaluated that the higher the absorbance, the higher the dissolution.

[0176] (Measurement of toluene elution of ultraviolet absorbers) For the resulting coated film, toluene elution was determined by the following method. From the obtained coating film, 0.2 g of a dried vinylidene chloride copolymer was collected by peeling and / or scraping with tweezers. The collected dried product was immersed in 10 mL of toluene and left for 12 hours. The dried product was removed from the toluene, and the absorbance of the toluene at a wavelength of 360 nm was measured using a UV-Visible Spectrophotometer UV1280 manufactured by Shimadzu Corporation. Reference: Sample solvent (THF if the sample was dissolved in THF) Cell: Quartz cell (optical path length 1 cm) When the absorbance exceeded 2.0, the solution was diluted so that the absorbance was between 0.1 and 1.0. The absorbance was calculated by multiplying the measured value by the dilution ratio. The absorbance was used as an index of dissolution, and it was evaluated that the higher the absorbance, the higher the dissolution.

[0177] (UV resistance evaluation) The ultraviolet resistance of the aqueous dispersion of the vinylidene chloride copolymer was measured. The measurement sample was prepared in the following manner. (Preparation of measurement samples) A water dispersion of vinylidene chloride copolymer was applied to aluminum foil at a dry coating weight of 10 g / m 2 The coating was applied with a Mayer bar so that the thickness of the coating was 100°C, and the coating was dried for 1 minute in an oven maintained at 100°C. The dried coating film was peeled off with tweezers within 5 minutes, and a single film of the aqueous dispersion (vinylidene chloride copolymer layer) was collected. The single film was folded four times to prepare a measurement sample. The single film was placed 30 mm from the light source ("LUV-16" manufactured by AS ONE) and irradiated with ultraviolet light from the light source for 5 hours in a room at 20°C. After irradiation, the yellowness YI was measured with a color difference meter according to the following (YI measurement method). The difference ΔYI (= YI - YI0) between the YI of the single film after ultraviolet irradiation and the YI of the single film before ultraviolet irradiation (YI0) was calculated, and it was evaluated that the smaller the ΔYI, the higher the ultraviolet resistance. (Method of measuring YI) The transmittance of the measurement sample was measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc. The average value of measurements obtained from three measurements was taken as the YI value. The measurement conditions were as follows. Color system: L*a*b* Index: YI ASTM E313-96 Field of view: 10° Main light source: D65 Secondary light source: None

[0178] (Recyclability evaluation) The coated film prepared using the aqueous dispersion of Example 4 was washed with tetrahydrofuran to completely remove the vinylidene chloride copolymer layer. The film was then dried and measured by ultraviolet-visible spectroscopy, and had the same spectrum as the film before the aqueous dispersion was applied. This means that the substrate film could be separated in a form that did not contain the ultraviolet absorber, demonstrating excellent recyclability.

[0179] The measurement and evaluation results of the examples and comparative examples are shown in Table 1. [Table 1-1]

[0180] [Table 1-2]

[0181] The above results demonstrate that the aqueous dispersion of the vinylidene chloride copolymer of the present invention (1) can impart gas barrier properties and UV absorbency to a substrate by itself when coated, and (2) can be separated from the substrate in a state free of UV absorbent by removing the coating layer. Furthermore, as the aqueous dispersion coating film of Comparative Example 5 did not exhibit ultraviolet light absorption, it was demonstrated that the aqueous dispersion of the present invention has remarkably superior ultraviolet light absorption properties to the aqueous dispersions simply containing an ultraviolet absorber, as described in References 1 to 7 and 10. [Industrial Applicability]

[0182] The aqueous dispersion of the vinylidene chloride copolymer of the present invention can impart gas barrier properties and ultraviolet absorbing properties by itself, and can be suitably used as a coating material for various materials such as packaging films for foods and medicines, paper, and general household goods.

Claims

1. An aqueous dispersion of a vinylidene chloride copolymer having an absorption coefficient of 0.01 L / (g cm) or more at a wavelength of 360 nm, The composition contains 0 parts by mass or more and less than 20 parts by mass of a polymer compound other than the vinylidene chloride copolymer, based on 100 parts by mass of the vinylidene chloride copolymer; The content of structural units derived from vinylidene chloride in the vinylidene chloride copolymer is 80% by mass or more.

1. An aqueous dispersion comprising:

2. 2. The aqueous dispersion according to claim 1, wherein an aqueous solution obtained by extracting the water-soluble component with water has an absorbance at a wavelength of 360 nm of less than 0.

4.

3. The aqueous dispersion according to claim 2 , further comprising a polymeric ultraviolet absorber.

4. The aqueous dispersion according to claim 3 , wherein the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer and a structural unit derived from vinylidene chloride.

5. 2. A film or paper laminate comprising a vinylidene chloride copolymer layer coated with the aqueous dispersion according to claim 1.

6. 1. A film or paper laminate comprising a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of a vinylidene chloride copolymer, the vinylidene chloride copolymer layer having an absorption coefficient of 0.01 L / (g cm) or more at a wavelength of 360 nm.

7. 7. A film or paper laminate according to claim 5 or 6, wherein said layers other than said vinylidene chloride copolymer layer are free of UV absorbers.

8. 7. A film or paper laminate according to claim 5 or 6, in which an aqueous solution obtained by extracting the water-soluble components with water has an absorbance at a wavelength of 360 nm of less than 0.

4.

9. 9. The film or paper laminate of claim 8, wherein said vinylidene chloride copolymer layer contains a polymeric UV absorber.

10. 10. The film or paper laminate of claim 9, wherein the vinylidene chloride interpolymer comprises structural units derived from ultraviolet absorbing monomers and structural units derived from vinylidene chloride.

Citation Information

Patent Citations

  • improvements in the polymerization of vinylidene compounds, in particular in the copolymerization of vinylidene chloride

    FR1466220A

  • Production of copolymer-coated material

    JP1985192768A

  • Ultraviolet screening laminated film

    JP1987263045A

  • Production of laminated plastic film

    JP1988128033A

  • Water-based polymer dispersion

    JP1993202107A